Anthropogenic microparticles across intertidal, shallow and mesophotic reef sediments in the Southwestern Atlantic - Yasmin Barros; Marcelo O. Soares; Alejandro P. Ayala; Vasco S. Neto; Jessica Reichert; Ítalo B. Castro; Tommaso Giarrizzo; Rivelino M. Cavalcante (Marine Pollution Bulletin, 2026)

Far from the coast: organohalogen bioaccumulation in spinner dolphins from the Southwestern Atlantic - Caroline A.C. Corrêa; Bárbara M.R. Manhães; Nara Oliveira-Ferreira; Elitieri B. Santos-Neto; Eduardo R. Secchi; Juliana C. Di Tullio; Rodrigo C. Genoves; Haydée A. Cunha; Tatiana L. Bisi; Alexandre F. Azevedo; José Lailson-Brito (Marine Pollution Bulletin, 2026)

Study of strontium hexaferrite prepared by solid state reaction using celestite and hematite - J. B. Neto; C. H. N. Cordeiro; M. M. de Góis; J. Xavier; J. M. Soares (Physics and Chemistry of Minerals, 2026)
Strontium hexaferrite (SrM) powders were prepared by solid-state reaction using celestite and magnetite/hematite. Energy dispersive X-ray fluorescence spectrometry, X-ray diffractometry (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometry were used for analyses. The precursor ores were purified by hand-sorting and magnetic separation. Magnetic separation yielded 75% magnetite and 25% hematite in iron ore. Strontium reached a single phase of $$\rm SrSO_4$$ via hand-sorting. XRD confirmed single-phase $$\rm SrFe_{12}O_{19}$$ sample with hexagonal symmetry (space group $$\rm P6_{3}/mmc$$ ). EDS analyse confirmed that the percentage of elements is in agreement with the expected stoichiometry for the hexaferrite phase. Initial SrM sample exhibited magnetization at maximum field of $$\rm 56~emu/g$$ and coercive field of $$\rm 632~Oe$$ . Although remanence and coercivity were lower than expected for the initial SrM sample, due to wide particle size distribution observed in SEM images, by optimizing synthesis parameters, particularly annealing at $$950^° $$ C, the coercivity increased by nearly eightfold, reaching 4.96 kOe. The sample annealed at 950 $$^° $$ C also exhibited a maximum energy product of $$\rm (BH)_{max}≈ 3.20~MGOe$$ and an estimated magnetocrystalline anisotropy constant of $$\rm K_1\sim 3.6× 10^6~erg/cm^3$$ . Microstructural evidence confirmed the predominance of particles in the monodomain regime, which justifies the increase in the coercive field. The results demonstrate that microstructural control is decisive for tuning the magnetic response of SrM, enabling the large-scale viability of this synthesis route for the production of high-coercivity hexaferrites, using a direct mixture of minerals instead of conventional industrial reagents.

A new Plasmodium Marchiafava & Celli, 1885 (Apicomplexa: Haemosporida) species in Cory’s Shearwater (Calonectris borealis) [Cory]) (Aves: Procellariiformes) stranded in a coastal area in Brazil - Carolina Clares dos Anjos; Bruna Antonetti Damato; Raquel Beneton Ferioli; Angélica M. Sánchez-Sarmiento; Amanda R. da Mata; Carla B. Barbosa; Hugo Gallo Neto; Carolina Romeiro Fernandes Chagas; Gediminas Valkiūnas; Karin Kirchgatter (Systematic Parasitology, 2026)
Cory’s Shearwater ( Calonectris borealis ), a migratory seabird from the Procellariidae family, is widely distributed across the Atlantic Ocean. It breeds on islands of Azores, Madeira, Canary, and Berlengas, and winters in coastal areas of South America and Africa. This species’ wide habitat range contributes to pathogen exchange across global regions. Plasmodium , a genus of apicomplexan parasites causing avian malaria, affects many wild bird species worldwide. Although rare in seabirds, Plasmodium infections can significantly impact these hosts. We identified and characterized a new Plasmodium species in an adult male C. borealis found live-stranded on the northern coast of São Paulo, Brazil, during the daily activities of the Santos Basin Beach Monitoring Project (PMP-BS). The bird was rescued and kept in rehabilitation for 61 days but was euthanized due to poor prognosis. Blood smears revealed parasitemia varying from 0.04% until 2.09%. Blood and tissue samples were tested using PCR targeting a cytochrome b ( cytb ) gene fragment. The obtained sequence was 100% similar to Plasmodium lineage pLK06. Phylogenetic analysis placed the parasite within the Novyella clade, with morphological features closely related to P. vaughani . Necropsy showed hepato- and splenomegaly, while histopathology confirmed hepatitis and pulmonary hemorrhage. These findings, combined with clinical relapse despite anti-malaria treatment, indicate the parasite’s pathogenicity in C. borealis . This represents the first haemosporidian infection in this seabird and the first identification of the pLK06 lineage in Procellariiformes, resulting in the description of Plasmodium borealis sp . nov . These findings expand knowledge of parasite diversity in seabirds and highlight the need for continued surveillance in understudied avian groups.

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

The Franciscana ( Pontoporia blainvillei ) in the Northern Limit of the FMA II : Strandings and Habitat Use in I lha G rande B ay - Alexandre F. Azevedo; Rafael R. Carvalho; Karina S. Pereira; Lis Bittencourt; Elitieri B. Santos‐Neto; Lara V. Pereira; Beatriz A. Santos; Gian Berardinelli; Haydée A. Cunha; Tatiana L. Bisi; José Lailson‐Brito (Marine Mammal Science, 2026)
The presence of the franciscana ( Pontoporia blainvillei ) at the northern limit of the FMA II was investigated using a range of methods, including monitoring of strandings, boat surveys, and passive acoustic monitoring (PAM). Franciscana strandings were recorded within the distributional gap between Macaé (22°55′ S) and Ilha Grande (23°09′ S), suggesting that the northern boundary of the FMA II may extend as far as Jaconé (22°56′ S; 42°38′ W). Furthermore, habitat use in Ilha Grande Bay was investigated through a combination of boat surveys and PAM efforts. Our findings support the idea that the species use Ilha Grande Bay year‐round, both day and night, and this bay might be the primary habitat of P. blainvillei in the FMA II section of the Rio de Janeiro coast. In Ilha Grande Bay, the franciscana is widely distributed over an area of more than 300 km 2 , along isobaths between 8 and 30 m. There were multiple detection events at the same PAM station during the day, indicating that the species was present at different times of day at the same location. Average group size was 7.7 (±6.7). While P. blainvillei occupies a large area of the bay, further investigation is needed into its use of shallower waters and the deeper, central portion of the bay, as well as the presence of areas with higher individual densities.

A live-feed hormone delivery protocol for the Siamese fighting fish (Betta splendens): Bioencapsulation of 17α-methyltestosterone in Artemia nauplii - Josué W. de Oliveira Neto; Daniel H. B. Padrão; José E. P. Cyrino; Brunno S. Cerozi (Aquaculture International, 2026)
The Siamese fighting fish ( Betta splendens ) is an ornamental fish commercially produced and exported worldwide. Male fish usually reach higher prices in the market, making masculinization protocols for producing male populations economically attractive. Steroid administration through dietary supplementation is one of the most commonly used methods for sex reversal in aquaculture. However, inert diets are not well accepted by B. splendens larvae. In this context, bioencapsulation techniques might represent an effective alternative for an oral hormone delivery during early development. This study developed a masculinization protocol for B. splendens using Artemia sp. bioencapsulated with 17α-methyltestosterone (17α-MT). Results showed that masculinization increased along with increasing 17α-MT enrichment, with the most consistent results observed at 30 and 40 mg L −1 , which yielded sex ratios above 0.85 compared with 0.50 in the control group. Fish weight, length, and survival rates were not affected by the tested concentrations of 17α-MT. These results demonstrate that the administration of androgen steroids bioencapsulated in Artemia nauplii could be considered an effective and safe strategy for the masculinization of B. splendens .

Olfactory bulb 6-OHDA neurotoxicity as a model of early cortical dysfunction - Edson Fiorenza-Neto; Bruna B. Gattiboni; Karin Almeida; Luis F. Marqueze; Bassam F. Mogharbel; Juliana R. N. de Aguiar; Larissa C. Marques; Larissa R. Lazarini; Stephanie R. S. Carvalhal; Angelica Boldt; Ricardo C. Cunha; Katherine A. T. Carvalho; et al. (Molecular and Cellular Biochemistry, 2026)
The olfactory bulb (OB) is one of the earliest brain regions affected in neurodegenerative diseases such as Parkinson’s disease (PD). Its high metabolic rate, dopaminergic modulation, and connectivity with the cortical and limbic regions make it particularly vulnerable to early neuroinflammatory and oxidative processes. This study aimed to investigate whether the administration of 6-hydroxydopamine (6-OHDA) into the OB induces behavioral, redox, and inflammatory alterations associated with early cortical disturbances. Male Wistar rats were randomly assigned to the sham or 6-OHDA groups and underwent stereotaxic injection of the vehicle or 6-OHDA into the left OB. Behavioral performance was assessed in the open-field test 12 days after surgery, and cortical tissue was collected for biochemical and molecular analyses. Cytokines (IL-1β, IL-6, TNF-α, IL-10, IFN-γ, and MCP-1) were quantified by Luminex, redox parameters (CAT, GPx, MDA, and protein carbonyls) by spectrophotometry, and neuronal signaling proteins (c-FOS, CREB, and BDNF) by qPCR. Animals with 6-OHDA lesions exhibited decreased latency and increased time spent in the central zone of the open field, indicating altered exploratory behavior. IL-6 levels were significantly elevated, whereas IFN-γ was reduced in the cortex, while IL-1β, TNF-α, MCP-1, and IL-10 remained unchanged. The oxidative stress markers MDA and protein carbonyls were increased, while catalase and glutathione peroxidase activities showed no change. The expression of c-FOS, CREB, and BDNF was not significantly modified. These findings indicate that localized 6-OHDA administration in the OB is sufficient to elicit behavioral, inflammatory, and oxidative alterations in connected cortical regions, which may resemble early non-motor features associated with olfactory dysfunction, without representing a neurodegenerative disease-specific process.

The anterograde tarsal venography enhances vessel visualization compared to the retrograde approach in horses - Daniel L. Parra-Torres; Gabriel B. Melo-Neto; Hector O. Garcia; Ana Paula A. Souza; Emanuel Vitor P. Apolonio; Celso Antônio Rodrigues; Ana Liz G. Alves; Carlos Alberto Hussni; Marcos J. Watanabe (The Veterinary Journal, 2026)

Influence of food resources and prey egg age on the predatory efficiency of phytoseiid mites associated with cashew - Luana Lima Melo; Josiane P. De Alfaia; João M. R. Costa; Antônio de A. P. Neto; Debora B. Lima; José W. S. Melo (Experimental and Applied Acarology, 2026)
Under field conditions, predator–prey interactions can be modulated by the diverse availability and suitability of food resources, which diet type may alter biological and behavioral parameters of predators. Amblyseius largoensis and Euseius concordis are phytoseiid predatory mites identified as potential biological control agents for the giant whitefly, Aleurodicus cocois , a major pest of cashew trees. In the present study, we investigated how exclusive and mixed diets composed of Ricinus communis pollen, A. cocois eggs, and Tetranychus urticae (used for comparison, as it is a standard prey in phytoseiid predation analysis) affect oviposition and predation by A. largoensis and E. concordis . In addition, we examined the effect of A. cocois egg age on consumption and feeding preference by these predators. Both species exhibited higher oviposition rates when fed exclusively on pollen, whereas diets composed solely of T. urticae resulted in the lowest values. The presence of pollen did not affect the predation rate of A. cocois eggs, indicating that the availability of this alternative resource does not compromise predatory efficiency. The age of A. cocois eggs offered as food did not affect predator oviposition; however, in both choice and no-choice tests, A. largoensis and E. concordis preferentially consumed older eggs (> 48 h). These results demonstrate that pollen availability increases reproductive potential without reducing predation capacity and that prey egg age influences consumption dynamics, providing ecologically relevant insights for management strategies that integrate the conservation of floral resources and the use of these phytoseiid mites in the biological control of A. cocois in cashew production systems.

Long-range transport of POPs to the central Atlantic Ocean: using a resident population of bottlenose dolphins (Tursiops truncatus) as sentinel species - Nara de Oliveira-Ferreira; Lilian Sander Hoffmann; Bárbara M.R. Manhães; Elitieri B. Santos-Neto; Marcelo Merten Cruz; Cristina Araujo Matzenbacher; Haydée Andrade Cunha; Tatiana Lemos Bisi; Alexandre de Freitas Azevedo; Thales Renato Ochotorena de Freitas; José Lailson-Brito (Marine Pollution Bulletin, 2026)

Pulmonary fibrosis in horses associated with spontaneous Crotalaria juncea intoxication - Andrezza C. Andrade; Silvio M.C. Fonseca; Givaldo B. Silva Filho; Elizandra T. Melo; José R.P. Santos; Maria Luiza S.L. Frota; Jean M.B.S. Duarte; Joaquim Evêncio-Neto; Luiz B. Brito; Telma S. Lima; Nathalia S. Wicpolt; Franklin Riet-Correa; et al. (Toxicon, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Flower-like WO3-modified Vulcan carbon GDEs for photoelectro-Fenton process: Efficient ciprofloxacin degradation and mechanistic insights - João Paulo C. Moura; Vanessa S. Antonin; Caio Machado Fernandes; Aline B. Trench; Erica S. Conrado; Michell O. Almeida; Kathia M. Honorio; Renata Colombo; Rafael Sotana; Ana M.P. Neto; Mauro C. Santos (Journal of Environmental Management, 2026)

Mycobiogenic silver nanoparticles enhance sorghum growth and salinity tolerance by modulating photosynthesis and oxidative responses - Ana B. S. Ziotti; Cristiane A. Ottoni; Vitória C. P. Kühl; Milton C. Lima Neto (Theoretical and Experimental Plant Physiology, 2026)
Adverse environmental conditions, including salinity, significantly threaten crop production worldwide, necessitating innovative strategies to improve plant resilience. This study comprehensively compared the effects of mycobiogenic (AgNP b ) and synthetic (AgNP s ) silver nanoparticles with ionic silver (AgNO 3 ) on sorghum growth and physiology. We also evaluated AgNP b seed priming to mitigate salinity effects, hypothesizing that salinity tolerance conferred by this priming is mediated by optimizing photosynthesis and enhancement of the antioxidant defense system, leading to reduced oxidative damage. In an initial experiment, sorghum seeds were treated with 0, 1.1 mg L -1 , or 10.8 mg L -1 of each silver form. AgNO₃ at 10.8 mg L -1 proved highly phytotoxic, inhibiting germination, reducing biomass, and inducing severe oxidative imbalance (elevated H₂O₂ and TBARS). In contrast, AgNP b exhibited lower toxicity and, at 10.8 mg L -1 , promoted sorghum growth and increased photosynthetic performance. Synthetic AgNP s showed intermediate effects. Crucially, in a subsequent experiment, AgNP b seed priming (1.1 mg L -1 ) successfully mitigated salinity effects (100 mM NaCl), improving photosynthetic efficiency and reducing oxidative damage markers in salt-exposed seedlings compared to non-primed controls. Our findings demonstrate that the form of silver (ionic vs. NP; biogenic vs. synthetic) is a critical determinant of phytotoxicity. Mycobiogenic AgNPs show significant potential for both growth promotion and, via priming, enhancement of salinity tolerance.

Repellent activity and toxicity of the essential oil of Calyptranthes concinna DC. using the model insect Drosophila melanogaster - M. S. Costa; T. S. Freitas; M. A. S. Oliveira; N. J. S. Araujo; S. P. Silva; Z. S. Silveira; N. S. Macêdo; J. C. Andrade-Pinheiro; H. S. Santos; A. M. R. Teixeira; F. A. B. Cunha; Ivo C. Pita Neto; et al. (Brazilian Journal of Botany, 2026)
Insects, belonging to the phylum Arthropoda, play essential roles in ecosystems, play essential roles in ecosystems, such as pollination, pest control, and decomposition. However, some species are vectors of diseases, which makes the development of control methods crucial. The use of synthetic insecticides, although effective, causes serious environmental and health problems. As an alternative, plant essential oils, which are biodegradable and can have repellent and toxic effects on insects, have gained prominence. This study focuses on the species Calyptranthes concinna DC., belonging to the Myrtaceae family, whose repellent and toxicological properties were evaluated using Drosophila melanogaster Meigan (1830) as an experimental model. The botanical material of Calyptranthes concinna was collected from the Private Natural Heritage Reserve in Palmeira-PR, and the essential oil was extracted from the dried leaves by hydrodistillation. The oil, with a yield of 0.26%, was stored for later analysis. The species Drosophila melanogaster was used as a model for toxicity and repellent activity tests. The tests involved fumigation of flies with different doses of oil, evaluation of damage to locomotor capacity and repellency test using filter paper. Data were analyzed statistically using two-way ANOVA. Calyptranthes concinna essential oil demonstrated low toxicity to Drosophila melanogaster , with 100% survival at all concentrations tested over 48 h and deaths that were not statistically significant compared to the water control. Impairment of locomotor capacity was observed only at the highest concentrations (40 µg/mL) after 3 h, and at intermediate concentrations (20 µg/mL) after 6 h, but these effects were equal to the control after 12 h. The repellency test revealed that the essential oil has a significant efficacy, especially at higher concentrations (39 µg/cm 2 ), comparable to the commercial repellent DEET, indicating that C. concinna essential oil is a promising alternative to synthetic repellents. Calyptranthes concinna essential oil has demonstrated potential as a natural repellent, with low toxicity and efficacy comparable to commercial DEET. Compared to studies with other essential oils and similar compounds, C. concinna oil has shown consistent results, suggesting that it may be an effective and environmentally friendly alternative to synthetic repellents. The presence of terpenes in the essential oil may be related to its repellent effect. These results support the use of C. concinna essential oil as a promising natural repellent.

Hydrodynamic control over shallow ferromanganese crust deposits in the West Rio Grande Rise - Pedro W.M. Souza-Neto; Muhammad Bin Hassan; João P.M. Amorim; Milton Borges-Silva; Cesar B. Rocha; Ilson C.A. da Silveira (Regional Studies in Marine Science, 2026)

Lactate as co-substrate to biostimulate sulfidogenic bioreactors using brewery spent grain as slow-release electron donor for acid mine drainage treatment - Guilherme S. Peres Neto; Rachel B. Costa; Piet N.L. Lens; Denise Bevilaqua (Journal of Water Process Engineering, 2026)

Higher education settings menus have low compliance with the Mediterranean Diet and high carbon and water footprint: a case study from Portugal, Croatia and Turkey - B. Neto; D. Dikmen; L. Ferreira; C. Viegas; S. Filipec; L. Drobac; Z. Šatalić; A. Rocha (International Journal of Gastronomy and Food Science, 2026)

Prospection of Autochthonous Lactic Acid Bacteria Displaying Probiotic Potential to Enhance Colossoma macropomum Larvae Growth and Immunoprotection Against Aeromonas hydrophila - Thayná M. dos Santos; Layana A. B. Pereira; Laine P. C. dos Santos; Andrya L. Lopes; Larissa A. F. Sampaio; Graziella V. G. de Matos Silva; Juliana N. Ferreira; Gleika T. J. Dos Reis; Jonny B. Teixeira; Raimundo J. T. Diniz‐Neto; Laura G. M. de Carvalho; Michelle Midori Sena Fugimura; et al. (Journal of Fish Diseases, 2026)
This study assessed the functional potential of autochthonous lactic acid bacteria isolated from the gastrointestinal tract of tambaqui ( Colossoma macropomum ) as larviculture probiotics. Five strains were selected and identified as belonging to the genus Weissella . In vitro assays revealed high tolerance to acidic pH (2.0–3.0), resistance to bile salts (10%), biofilm formation capacity, hydrophobicity and direct Aeromonas hydrophila inhibition. In in vivo tests, strains M13 and M14 promoted significant increases in tambaqui survival (72.2% and 68.7%; p

Toxic myopathy in dairy goats caused by spontaneous ingestion of Senna obtusifolia - Silvio M.C. Fonseca; Fernanda P.S. Barbosa; Natália S. Wicpolt; Telma S. Lima; Givaldo B. Silva Filho; Elizandra T. Melo; José R.P. Santos; Maria Luiza S.L. Frota; Joaquim Evêncio Neto; Franklin Riet-Correa; Fábio S. Mendonça (Toxicon, 2026)

Impacts of Rapid Development in a Subtropical Region of South America (Rio de Janeiro, Brazil): Insights from Emerging Contaminants Across Various Chemical Classes - Moises L. Gil; Daniele M. Bila; Estefan M. Fonseca; Jose A. B. Neto; Lucas B. Moreira; Rivelino M. Cavalcante (Water, Air, & Soil Pollution, 2026)

Distribution and status of Smicridea McLachlan, 1871 (Trichoptera: Hydropsychidae) in the Rio Doce Basin, Southeastern Brazil a decade after the tailings dam disaster - Ana Dária L. Viana; Pedro Bonfá-Neto; Gleison R. Desidério; Ana R. B. Izidoro; João V. M. Curi; Frederico F. Salles (Biologia, 2025)

Chemical and toxicological evaluation of micropollutants degradation in tertiary municipal wastewater by H2O2/UVC - Gabrielly M. Santos; Lucas G. Costa; Eduardo O. Marson; Meliza A.S. Bessa; Raquel W. Becker; Carla F.G. Frois; Carla Sirtori; Adão S. Ferreira; Raquel M.F. Sousa; Waldomiro Borges Neto; Marcelo B. Santos; Solidônio R. Carvalho; et al. (Journal of Environmental Chemical Engineering, 2025)

Leaf Nitrogen Spraying Improves Photosynthesis, Seed Quality and Yield of Soybean Plants Facing post-flowering Phosphorus Deficiency - Matheus D. Laira; Tamires S. Martins; Rafael L. Almeida; Venancio F. de Moraes-Neto; Juliana A. L. Pallone; Fernando C. B. Zambrosi; Rafael V. Ribeiro (Journal of Soil Science and Plant Nutrition, 2025)

Expanding the repertoire of conopeptides from the venom of the vermivorous snail Conus regius - Helena B. Fiorotti; Suely G. Figueiredo; Emídio Beraldo-Neto; Fabiana V. Campos; Daniel C. Pimenta (Toxicon, 2025)

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

An experimental test on the effects of dispersal from different habitat sources on community structure - Gustavo L. Villarreal; Fernanda A. S. Cassemiro; Priscilla Carvalho; Luis M. Bini; Jascieli C. Bortolini; Amanda C. F. Queiroz; Wilson M. Leão‐Neto; Roger P. Mormul; Ludgero C. G. Vieira; João C. Nabout; Fabricio B. Teresa; Maisa C. Vieira; et al. (Ecology, 2025)
Biological interactions, disturbances, and demographic stochasticity often drive population declines and local extinctions. Dispersal can counterbalance these drivers by rescuing small populations or facilitating recolonization. Using freshwater zooplankton in experimental mesocosms, we tested three hypotheses: (1) isolated sites would experience declines in species richness, with ecological drift causing communities to lose different species and become more dissimilar over time; (2) communities connected by dispersal from similar habitats would maintain their species richness and composition, as arriving species balance losses through rescue effects and recolonization, thereby halting community differentiation; and (3) dispersers originating from different sources may establish themselves in recipient communities through mass effects, resulting in higher species richness compared to communities receiving dispersers from similar habitat sources. Thirty 500‐L tanks were initially colonized with zooplankton from lake A, and 10 tanks with colonizers from lake B, which had partially distinct species composition. Tanks were kept isolated for 50 days, after which 10 tanks initially colonized by lake A began receiving dispersers from paired tanks also colonized by lake A (treatment Aa). Another 10 tanks colonized by lake A received dispersers from paired tanks colonized by lake B (Ab). We found that isolated communities (A0, B0) tended to lose species over time and differentiate from one another, indicating differential local extinctions. Communities receiving dispersers from the same habitat (Aa) halted species losses and maintained their species richness, whereas those receiving species from a different habitat (Ab) not only halted species losses but also accumulated additional species over time. Treatments receiving dispersers (Aa, Ab) exhibited beta diversity (among replicates within treatments) similar to levels observed prior to dispersal events. Comparisons of paired source‐recipient tanks (A0–Aa, B0–Ab) further supported the finding of differential extinctions in isolated communities. Our results demonstrate that dispersal counteracts declining species richness and increasing differentiation caused by differential local extinctions in isolated communities, either through rescue or mass effects.

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

An outbreak of Urochloa decumbens intoxication in goats from Northeast Brazil - Silvio M.C. Fonseca; Givaldo B. Silva Filho; Elizandra T. Melo; Andrezza C. Andrade; José R.P. Santos; Maria Luiza S.L. Frota; Joaquim Evêncio-Neto; Telma S. Lima; Paula R. Pereira; David Driemeier; Fábio de Souza Mendonça (Toxicon, 2025)

Paths to prosperity: How transport networks and income accessibility shape retail location - José B. Paiva Neto; Narciso F. Santos; Romulo D. Orrico Filho (Journal of Transport Geography, 2025)

The legacy and future of multiple anthropogenic stressors: Organohalogen compounds in the vulnerable Guiana dolphin (Sotalia guianensis) - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Monizze Vannuci-Silva; Adriana Castaldo Colosio; Hernani Gomes da Cunha Ramos; Ian Augusto Gusman Cunha; Lupércio Araújo Barbosa; Ana Paula Cazerta Farro; Drienne Messa Faria; Haydée A. Cunha; Tatiana L. Bisi; et al. (Journal of Hazardous Materials, 2025)

The silent adjuvant interaction on the predatory behavior and video tracking with computerized analysis on Marava arachidis (Yersin) (Dermaptera: Labiidae) - Taiane G.F. da Silva; Angélica da Silva Salustino; Jaime G. da Silva Neto; Jacinto de L. Batista; Érica K. de Araújo; Iago V.I. da Silva; Carla R.S.M. Viagem; Luciana B. Silva; Carlos H. de Brito; Khyson G. Abreu; Robério de Oliveira; José B. Malaquias (Environmental Pollution, 2025)

Invasive whistling frogs (Eleutherodactylus johnstonei) act as a reservoir for antimicrobial-resistant Enterobacteriaceae in Latin America's most populous city - Gabrielli S. Abreu; Gabriel S. dos Santos; Denise B. Nogueira; Gissandra F. Braz; Rafael R. Soares; Nathália S. Guimarães; Gisele O. de Souza; Cinthia A. Brasileiro; José S. Ferreira Neto; Marcos B. Heinemann (Veterinary Research Communications, 2025)

Acoustic parameter variation and emission patterns in franciscana dolphin (Pontoporia blainvillei) clicking behavior at high frequency - Lis Bittencourt; Rafael R. Carvalho; Karina Pereira; Elitieri B. Santos-Neto; Jose Lailson-Brito; Tatiana L. Bisi; Alexandre F. Azevedo (Frontiers in Marine Science, 2025)
Franciscana dolphins are small odontocetes that produce narrow-band high-frequency echolocation clicks. Autonomous acoustic monitoring and field survey acoustic sampling were used to record franciscana dolphins in Ilha Grande Bay, Brazil. Clicking sequences were automatically detected and analyzed, and then manually classified into different types; acoustic parameters from individual clicks were extracted. A total of 12505 clicks were detected, 152 clicking sequences were analyzed, of which 43 were click trains and 109 were click packets. Considering all clicks, they occurred from 88.7 kHz to 250 kHz, with a mean peak frequency of 132.4 ± 6.8 kHz. Click trains were longer than click packets, with larger inter-click intervals and mean peak frequencies of 123.6 ± 16.4 kHz and 119.9 ± 15.0 kHz, respectively. Franciscana dolphins emitted different types of clicking sequences. The use of patterned clicks by franciscana dolphins may be an important communication feature at very high frequencies.

β-Lactam Potentiating Activity, Molecular Docking, and ADMET Analysis of 3-Substituted Coumarins - José B. de Araújo-Neto; Daniel S. Alves; Gildênia A. de Araújo; Fernanda R. Ribeiro; Guilherme A. Brancaglion; Diogo T. Carvalho; Henrique D. M. Coutinho; Augusto Schrank; Saulo R. Tintino (Current Microbiology, 2025)

Austral Autumn Precipitation Anomalies Across the Amazon Basin Under the Combined Influences of the Equatorial Pacific and Tropical Atlantic - Antônio V. Nogueira Neto; Everaldo B. de Souza; Fernanda C. Vasconcellos; Douglas Silva Ferreira; Vania S. Franco; Claudia P. W. da Costa; Edmir S. Jesus; Renata G. Tedeschi (International Journal of Climatology, 2025)
Under normal conditions, the austral autumn (March–April–May [MAM]) season represents the onset, peak or end of the rainy season, depending on the Amazon sector. In this study, the relative influences of the equatorial Pacific (EqP) and tropical Atlantic (TA) on precipitation anomalies over northern South America were revisited, focusing on the Amazon Basin and the MAM season. We systematically analysed the combined and isolated influences of the EqP and TA to identify the regions of the Amazon that are most sensitive to the atmospheric and oceanic patterns during MAM and described the main related mechanisms responsible for anomalous precipitation. The main features of the El Niño‐Southern Oscillation (ENSO) and the TA meridional sea surface temperature gradient (tropical Atlantic gradient—TAG) were described for each scenario. Our results indicate that a positive (negative) TAG alone increases (decreases) precipitation over the northern and central‐eastern regions. On the other hand, the isolated influence of ENSO depends on its persistence during the season, affecting mainly the northern and north‐eastern regions, with a stronger impact on La Niña occurrence. Under the occurrence of ENSO events and TAGs of the same sign, the whole equatorial Amazon is affected by the sum of circulation effects. In this context, the driest scenario was observed under the combined influence of an El Niño and a positive TAG, which strongly impacted the northern and central‐eastern sectors of Amazon. Finally, TAGs and ENSO events of opposite signs resulted in anomalous precipitation mainly in the northern, north‐eastern and western Amazon, where the TAG‐related circulation prevailed against the influence of ENSO events. This study improves the current understanding of austral autumn spatial rainfall variability in the Amazon under the influence of ENSO and tropical Atlantic patterns.

Intrauterine growth restriction (IUGR) modifies the hypothalamic response to a systemic glucose load in adult male rats, as assessed by proteomic analysis - Thais A. J. Mutran; Amanda P. Pedroso; Adriana P. de Souza; Valter T. Boldarine; Antonio M. M. Neto; Claudia B. Angeli; Lila M. Oyama; Giuseppe Palmisiano; Eliane B. Ribeiro; Monica M. Telles (Metabolic Brain Disease, 2025)

Metagenomic and morphological analysis of biodeteriogenic biofilms on historic stone buildings in the tropical north-east of Brazil - Christine C. Gaylarde; Beata Gutarowska; Iwona B. Beech; Justyna Szulc; Amit Acharjee; Tomasz Grzyb; Alex da Silva de Freitas; José Antônio Baptista Neto (International Biodeterioration & Biodegradation, 2025)

Towards a climate-resilient conservation network in Portugal - Miguel B. Araújo; Diogo Alagador; Babak Naimi; Dora Neto; Alejandro Rozenfeld (Biological Conservation, 2025)

Insecticidal efficacy and chemical profile of Handroanthus impetiginosus extracts for sustainable management of the coffee leaf miner (Leucoptera coffeella) - Andriely B. Silva; Daniel L. Montagnini; Albert Katchborian-Neto; Miller Santos Ferreira; João V. Andrade; Guilherme Otoni Francisco; Pedro S. S. R. Cavallari; Samarah G. Almeida; Enes P. Barbosa; Wilson R. Cunha; Marisi G. Soares; Murilo de Oliveira Souza; et al. (Journal of Plant Diseases and Protection, 2025)

Quantification of alcohol content and identification of fraud in traditional cachaças using NIR spectroscopy - Valber Elias de Almeida; José Félix de B. Neto; Taliana Kênia A. Bezerra; Vanessa P. da Silva; Germano Veras; Railson de Oliveira Ramos; David Douglas de Sousa Fernandes (Food Chemistry, 2025)

Impact of sublethal treatments on dormant and non-dormant populations of Bacillus cereus spores during spray drying and on their recovery during whole milk powder storage - Verônica O. Alvarenga; Fernanda B. Campagnollo; Rosicléia A. Silva; Miriam D. Hubinger; Émilie Lang; Dionisio P. Amorim-Neto; Anderson S. Sant’Ana (International Dairy Journal, 2025)

Correction: Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2025)

Mapping Anatomical Landmarks of the Cerebellum Central Core: Enhancing Precision in Surgical Interventions for Cerebellar Lesions - Luis Gustavo Biondi-Soares; Richard Gonzalo Párraga; Rene Alejandro Apaza-Tintaya; Lucca B. Palavani; Veronica Alzate-Carvajal; Felipe Salvagni; Alexander Feliciano Vilcahuaman Paitán; Gabriel Ataide Monção; Luis Ángel Canache Jiménez; Raphael Wuo-Silva; Feres Chaddad-Neto (The Cerebellum, 2025)

Biosorption assessment of emerging contaminants onto acidogenic and methanogenic biofilm reactors: Influence of lipophilic and electrostatic interactions - Rodrigo B. Carneiro; Paula Y. Takeda; Maria E.S. Dias; Elis W. Nogueira; Marcelo Zaiat; Álvaro J. Santos-Neto (Journal of Environmental Chemical Engineering, 2025)

Land-use change and deep-soil carbon distribution on the Brazilian Amazon-Cerrado agricultural frontier - Gustavo V. Popin; Maria Eduarda B. de Resende; Jorge L. Locatelli; Rafael S. Santos; Marcos Siqueira-Neto; Paulo M. Brando; Christopher Neill; Carlos E.P. Cerri (Agriculture, Ecosystems & Environment, 2025)

Abundance of two Guiana dolphin ( Sotalia guianensis ) populations inhabiting adjacent areas in southeastern Brazil - Rafael R. Carvalho; Carlos Eduardo P. Quintana; Carlos Vinícius C. dos Santos; Elitieri B. Santos‐Neto; Lis Bittencourt; Karina S. Pereira; Tatiana L. Bisi; Maja Kajin; José Lailson‐Brito; Alexandre F. Azevedo (Marine Mammal Science, 2025)
Guiana dolphins ( Sotalia guianensis ) are commonly found in shallow waters from South and Central America. From March 2018 to June 2019, boat surveys were conducted to monitor two populations inhabiting the adjacent waters of Ilha Grande Bay and Sepetiba Bay to estimate population abundances and population parameters of apparent survival and capture probability. Photo‐identification was used as a mark‐recapture technique. A total of 672 dolphins was cataloged in Ilha Grande Bay and 826 in Sepetiba Bay, with two individuals being photographed in both areas. Population parameters were estimated through mark‐recapture models and total population abundance was estimated at 1,949 and 1,560 individuals in Ilha Grande Bay and Sepetiba Bay, respectively. Seasonal estimates were modeled showing that the Sepetiba Bay population may have stronger site fidelity to the study area than individuals in Ilha Grande Bay. Apparent survival was estimated in a mixed model framework avoiding bias due to the large presence of transient individuals. The estimates presented here are a result of an effort conducted months after an unusual mortality event linked to Guiana dolphin cetacean morbillivirus and our findings indicated that surviving individuals did not have long‐term deadly effects, but continuous efforts should be considered for a long‐term evaluation.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

When zombies go vegan: Ophiocordyceps unilateralis hosts are selecting to bite palm leaves before dying? - Fernando S. Andriolli; J. Aragão Cardoso Neto; Paul V.A. Fine; Diego Salazar; Giovanna Figueroa; Diego V. Torres; J. Wellington de Morais; Fabricio B. Baccaro (Acta Oecologica, 2025)

Cost-effective alternatives to facilitate biomonitoring and bioassessment of neotropical streams - Francisco Valente-Neto; Renato B. Dala-Corte; Almir M. Cunico; André L.B. Magalhães; Bruno S. Godoy; Cecília G. Leal; Diego M.P. Castro; Diego R. Macedo; Dilermando P. Lima-Junior; Éder A. Gubiani; Fabio de O. Roque; Fabrício B. Teresa; et al. (Science of The Total Environment, 2025)

Confounding factors in the isotopic analysis of herbivore fecal samples - Isabela Pivetta Trentini; Marcelo Magioli; Francisco Grotta-Neto; Pedro Henrique de Faria Peres; Katia Maria P M B Ferraz; Marcelo Zacharias Moreira; Márcio Leite de Oliveira; José Maurício Barbanti Duarte (European Journal of Wildlife Research, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Enhancing Sustainability and Conservation of White Shrimp Penaeus schmitti in Northeast Brazil: Insights Into Life History, Reference Points, and Management Strategies for Beach Seining - Hildemário Castro‐Neto; Cecília Craveiro; Lucas Santos; Emanuell F. B. Silva; Roberta Soares; Sílvio Peixoto (Fisheries Management and Ecology, 2025)
Artisanal fishing significantly not only contributes to socioeconomic development of numerous countries but also exerts pressure on natural populations. The white shrimp ( Penaeus schmitti ) is a key species in Brazilian artisanal fisheries, yet it is currently classified as data‐deficient. Conducting comprehensive studies on its population dynamics is essential to establish reference points that guarantee sustainable fishing. Therefore, we estimated population parameters to assess status of the white shrimp stock captured by beach seining in Northeast Brazil. Monthly samples of white shrimp were collected using a beach trawl. Based on population parameters, the white shrimp population in the study area, the sex ratio was 1 male to 1.29 females, with females larger and heavier than males. Weight–length relationships revealed positive allometric growth for males, females, and grouped sexes, with no significant difference between sexes. Asymptotic length, t_achor, and growth performance index also did not differ between sexes; however, the growth coefficient was higher for females. Beach trawling in northeastern Brazil predominantly targeted adult white shrimp, with carapace length at first capture (Lc 50 ) averaging 2.12 cm for females and 2.19 cm for males. Mortality and exploitation rates were below maximum sustainable levels, so the stock was classified as underexploited. Overall, beach‐seine fishing was less harmful to this stock ( F = 1.42) than motorized fishing and can be considered a sustainable fishing activity for the white shrimp population.

Beyond the threshold - Different accumulation of organochlorine compounds in common dolphins (Delphinus delphis) inhabiting continental and insular ecosystems in the Northeast Atlantic - Raul Valente; Nara de Oliveira-Ferreira; Rita Ferreira; Ana M. Correia; Bárbara M.R. Manhães; Ágatha Gil; Annalisa Sambolino; Elitieri B. Santos-Neto; L. Filipe C. Castro; Haydée A. Cunha; Alexandre F. Azevedo; Ana Dinis; et al. (Environmental Pollution, 2025)

Unraveling the evolution of the Bodó W-skarn district in the Seridó Mineral Province (NE-Brazil): constraints from C-O stable isotopes, thermodynamic modeling, and geochronology - Dinarte Lucas; Maria Helena B. M. Hollanda; João Adauto de Souza Neto; Renato Moraes; Laécio Cunha de Souza (Mineralium Deposita, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Insecticidal activity of extracts of handroanthus impetiginosus on Plutella xylostella (Lepidoptera: plutellidae) larvae - Andriely B. Silva; Daniel L. Montagnini; Albert Katchborian-Neto; João V. Andrade; Hallana A. Manuquian; Pedro S. S. R. Cavallari; Samarah G. Almeida; Enes P. Barbosa; Wilson R. Cunha; Marisi G. Soares; Mario F. C. Santos; Márcio L. A. Silva; et al. (Natural Product Research, 2024)

Biotransformation pathways of pharmaceuticals and personal care products (PPCPs) during acidogenesis and methanogenesis of anaerobic digestion - Rodrigo B. Carneiro; Rubén Gil-Solsona; Jessica Subirats; Esteban Restrepo-Montes; Marcelo Zaiat; Álvaro J. Santos-Neto; Pablo Gago-Ferrero (Journal of Hazardous Materials, 2024)

Investigation of Rabies virus in wild mammals of the atlantic forest in Rio de Janeiro, Brazil - M. Cocchi; C. M. Barboza; J. G. Garcia; R. M. Zamudio; A. Champi; R. L. M. Novaes; S. F. Costa-Neto; R. Moratelli; H. B. C. R. Batista (Brazilian Journal of Microbiology, 2024)

Optimizing ReBreed21 II: Fertility and reproductive efficiency in different parities during a shortened breeding season in beef cattle - João Paulo N. Andrade; Pedro J.L. Monteiro; Alexandre B. Prata; Adelino J. Robl; José Neto; Beatriz Lippe; Heuller S. Ribeiro; Diego Hartmman; Roberto Sartori; Milo C. Wiltbank (Theriogenology, 2024)

The fate of Salmonella enterica and Listeria monocytogenes in the pulp of eight native Brazilian and exotic fruits - Beatriz S. Silva; Dionisio P. Amorim-Neto; Arthur K.R. Pia; Fernanda B. Campagnollo; Marianna M. Furtado; Ana Carolina B.R. Carvalho; Juan M. Oteiza; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2024)

Genomic analysis of the first multidrug-resistant ESBL-producing high-risk clonal lineage Klebsiella pneumoniae ST147 isolated from a cat with urinary tract infection - Victoria T. S. Sakauchi; Amanda Haisi; João P. Araújo Júnior; José S. Ferreira Neto; Marcos B. Heinemann; Natália C. Gaeta (Veterinary Research Communications, 2024)

Evaluation of evaporation methods for modelling rainfall interception in a dry tropical forest - Antonio José Steidle Neto; Daniela C. Lopes; Thieres G. F. Silva; Luciana S. B. Souza (Theoretical and Applied Climatology, 2024)

Bioadhesive Polymeric Films Containing Rhamnolipids, An Innovative Antimicrobial Topical Formulation - Jéssica B. Carra; Kamila B. B. Wessel; Giovana N. Pereira; Mariana C. Oliveira; Pietra M. T. Pattini; Bianca L. Masquetti; Ismael R. Amador; Marcos L. Bruschi; Rúbia Casagrande; Sandra R. Georgetti; Waldiceu A. Verri; Gerson Nakazato; et al. (AAPS PharmSciTech, 2024)

Performance, nutrient utilization and meat quality traits in Bos indicus cattle: a meta-analysis examining the effect of residual feed intake - Daniela A. Vesga; Rodrigo N. S. Torres; José B. S. Moreira; Yury T. Granja-Salcedo; Otavio R. Machado Neto; Luis Artur L. Chardulo; Mahesh N. Nair; Pedro H. V. Carvalho; Welder A. Baldassini (Tropical Animal Health and Production, 2024)

Enterolith with a bonefish spine nidus in a Brazilian cownose ray Rhinoptera brasiliensis (Müller & Henle) (Myliobatiformes: Rhinopteridae) - L. O. Camilo; B. L. Maganhe; H. Gallo Neto; E. G. Sanches (Journal of Fish Diseases, 2024)
An adult female Brazilian cownose ray ( Rhinoptera brasiliensis ), housed in Ubatuba Aquarium died after loss of appetite period. During necropsy, an enterolith was discovered partially obstructing the intestinal lumen. Examination of the enterolith revealed a bonefish spine nidus. Enterolithiasis has been linked to multiple factors including diet, genetics, alkaline intestinal environments and, as in this particular case, the ingestion and retention of foreign bodies. The composition of this enterolith from a cownose ray was primarily monohydrocalcite. This short communication, apparently the first to report enterolithiasis in stingrays, emphasizes the need for post‐mortem examinations of carcasses on macroscopic and microscopic levels.

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Anaerobic co-metabolic biodegradation of pharmaceuticals and personal care products driven by glycerol fermentation - Rodrigo B. Carneiro; Gisele M. Gomes; Franciele P. Camargo; Marcelo Zaiat; Álvaro J. Santos-Neto (Chemosphere, 2024)

The Rio Grande Rise circulation: Dynamics of an internal tide conversion hotspot in the Southwestern Atlantic - Pedro W.M. Souza-Neto; Ilson C.A. da Silveira; Cesar B. Rocha; Cauê Z. Lazaneo; Paulo H.R. Calil (Progress in Oceanography, 2024)

Optimizing PtSn Composition in Direct Sugarcane Extract Fuel Cells: A Sustainable Bioenergy Solution - Bruno D. Q. Villardi; Victoria A. Maia; Julio Nandenha; Priscilla J. Zambiazi; Rodrigo F. B. de Souza; Almir O. Neto (Sugar Tech, 2024)

Genomic prediction and QTL analysis for grain Zn content and yield in Aus-derived rice populations - Tapas Kumer Hore; C. H. Balachiranjeevi; Mary Ann Inabangan-Asilo; C. A. Deepak; Alvin D. Palanog; Jose E. Hernandez; Glenn B. Gregorio; Teresita U. Dalisay; Maria Genaleen Q. Diaz; Roberto Fritsche Neto; Md. Abdul Kader; Partha Sarathi Biswas; et al. (Journal of Plant Biochemistry and Biotechnology, 2024)
Zinc (Zn) biofortification of rice can address Zn malnutrition in Asia. Identification and introgression of QTLs for grain Zn content and yield (YLD) can improve the efficiency of rice Zn biofortification. In four rice populations we detected 56 QTLs for seven traits by inclusive composite interval mapping (ICIM), and 16 QTLs for two traits (YLD and Zn) by association mapping. The phenotypic variance (PV) varied from 4.5% ( qPN 4.1 ) to 31.7% ( qPH 1.1 ). qDF 1.1 , qDF 7.2 , qDF 8.1 , qPH 1.1 , qPH 7.1 , qPL 1.2 , qPL 9.1, qZn 5.1 , qZn 5.2 , qZn 6.1 and qZn 7.1 were identified in both dry and wet seasons; qZn 5.1 , qZn 5.2 , qZn 5.3, qZn 6.2, qZn 7.1 and qYLD 1.2 were detected by both ICIM and association mapping. qZn 7.1 had the highest PV (17.8%) and additive effect (2.5 ppm). Epistasis and QTL co-locations were also observed for different traits. The multi-trait genomic prediction values were 0.24 and 0.16 for YLD and Zn respectively. qZn 6.2 was co-located with a gene ( OsHMA2 ) involved in Zn transport. These results are useful for Zn biofortificatiton of rice.

Ni supported on desilicated HZSM-5 as catalyst for biogas reforming - Lícia R.F. Coelho; Andressa A.A. Silva; Yutao Xing; Raimundo C. Rabelo-Neto; Fabio B. Noronha; Lisiane V. Mattos (Fuel, 2024)

Telocytes: current methods of research, challenges and future perspectives - Bruno D. A. Sanches; Francisco B. S. Teófilo; Mathieu Y. Brunet; Victor M. Villapun; Kenny Man; Lara C. Rocha; Jurandyr Pimentel Neto; Marta R. Matsumoto; Juliana S. Maldarine; Adriano P. Ciena; Sophie C. Cox; Hernandes F. Carvalho (Cell and Tissue Research, 2024)

Laser-induced breakdown spectroscopy (LIBS) as an analytical tool in precision agriculture: Evaluation of spatial variability of soil fertility in integrated agricultural production systems - Diego V. Babos; Amanda M. Tadini; Carla P. De Morais; Bianca B. Barreto; Mayara A.R. Carvalho; Alberto C.C. Bernardi; Patricia P.A. Oliveira; José R.M. Pezzopane; Débora M.B.P. Milori; Ladislau Martin-Neto (CATENA, 2024)

GIS-FA: an approach to integrating thematic maps, factor-analytic, and envirotyping for cultivar targeting - Maurício S. Araújo; Saulo F. S. Chaves; Luiz A. S. Dias; Filipe M. Ferreira; Guilherme R. Pereira; André R. G. Bezerra; Rodrigo S. Alves; Alexandre B. Heinemann; Flávio Breseghello; Pedro C. S. Carneiro; Matheus D. Krause; Germano Costa-Neto; et al. (Theoretical and Applied Genetics, 2024)

Multi-datasets to monitor and assess meteorological and hydrological droughts in a typical basin of the Brazilian semiarid region - Glauciene Justino Ferreira da Silva; Richarde Marques da Silva; Reginaldo Moura Brasil Neto; Jorge Flávio Casé B. C. Silva; Ana Paula Xavier Dantas; Celso Augusto Guimarães Santos (Environmental Monitoring and Assessment, 2024)

Resilience of Ricinus communis L. to high temperatures during germination and seedling growth resulting from efficient superoxide dismutase modulation - Valdir G. Neto; Wilco Ligterink; Henk W. M. Hilhorst; Isabela D. Santos; Carine R. Teixeira; Emily E. Santos; Marta B. Loureiro; Daniele Takahashi; Luzimar G. Fernandez; Paulo R. Ribeiro; Renato D. De Castro (Brazilian Journal of Botany, 2024)

Genetic parameters for host-response to acanthocephaliasis caused by the endoparasite Neoechinorhynchus buttnerae in the Amazon fish Colossoma macropomum - John F.G. Agudelo; Baltasar F.G. Neto; Vito A. Mastrochirico-Filho; Raquel B. Ariede; Luis F.S. Moreira; Leilane da Silva Noronha; José M. Yáñez; Alexandre Honczaryk; Gustavo M.R. Valladão; Diogo T. Hashimoto (Aquaculture, 2024)

Dwarf minke whales (Balaenoptera acutorostrata) acoustic signals from the South Atlantic Ocean - Lis Bittencourt; Rafael Carvalho; Elitieri B. Santos-Neto; Tatiana L. Bisi; Jose Lailson-Brito; Alexandre F. Azevedo (Frontiers in Marine Science, 2024)
At present, there are still populations of different balaenopterids that have never been acoustically recorded and observed simultaneously. In an opportunistic sighting of dwarf minke whales during winter in southeastern Brazil, we have registered six individuals and recorded over 200 acoustic signals. Signals were quantified and had their acoustic parameters extracted; the calling rate was estimated as the number of sounds per minute, and the repetition rate was estimated as the number of calls of the same type emitted per minute. Four call types were described: Ba1, Ba2, Ba3 and Ba4. The most common and distinctive call was the Ba1, composed of three components: one had a peak frequency of 615.0 ± 189.8 Hz, and the other had peak frequencies of 1632.0 ± 191.5 and 5038.2 ± 195.1 Hz. Ba1 repetition varied from 2.4 to 11.1 repetitions/min. Ba2 was the second most common call with a peak frequency of 485.2 ± 421.9 Hz. The total calling rate varied from 4.4 to 11.1 calls/min. The signals are in the same frequency range reported for other areas but contain different structures.

Ex vivo inhibition of PGE2 formation in human blood by four bicyclico [3.2.1] octane neolignans isolated from Aniba firmula bark, two with unusual structural pattern - Mario F. C. Santos; Karen de J. Nicácio; Albert Katchborian-Neto; Miller S. Ferreira; Daniel de Oliveira Miranda; João V. Andrade; Herinque de A. Pereira; Ester Gonçalves de Jesus; Thamires B; Silva Souza; Raquel P. Morais-Urano; Danielle Ferreira Dias; et al. (Natural Product Research, 2024)

Cardioprotective Effects of Leucine Supplementation against Doxorubicin-Induced Cardiotoxicity - Lucas C. Guimarães; Thiago M. Fidale; Talita C. R. Pereira; Paulo R. Lopes; Marcos D. Ferreira-Junior; Simone R. Deconte; Marcos L. Ferreira-Neto; Willams S. Brito; Rodrigo M. Gomes; Fernanda R. de Souza; Keilah V. N. Cavalcante; Gustavo C. Herrera; et al. (Cardiovascular Toxicology, 2024)

The deep dive of organohalogen compounds: Bioaccumulation in the top predators of mesopelagic trophic webs, pygmy and dwarf sperm whales, from the Southwestern Atlantic ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Vitor L. Carvalho; Letícia Gonçalves; Pedro V. de Castilho; Eduardo R. Secchi; Silvina Botta; Milton C.C. Marcondes; Adriana C. Colosio; Marta J. Cremer; Haydée A. Cunha; et al. (Chemosphere, 2023)

Application of two- and multiway chemometric strategies for describing elementomic changes in pepper plants exposed to cadmium stress by multielement determination - Marcos de O. Ribeiro; Claudia B. de Abreu; Cindy S. Pinho; Lucas de O. Ribeiro; André D. de A. Neto; Leonardo S.G. Teixeira; Silvana M. Azcarate; Fabio de S. Dias (Chemosphere, 2023)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Mitigating the capacity loss by crossover transport in vanadium redox flow battery: A chemometric efficient strategy proposed using finite element method simulation - Luis Felipe Pilonetto; Felipe Staciaki; Eryka Nóbrega; Evaldo B. Carneiro-Neto; Jeyse da Silva; Ernesto Pereira (Chemical Engineering Journal, 2023)

Adaptation and application of the fuzzy synthetic evaluation (FSE) method for characterizing the trophic state of tropical semiarid reservoirs - João B. S. Raulino; Iran E. Lima Neto (Environmental Monitoring and Assessment, 2023)

United we stand, divided we fall: in-depth proteomic evaluation of the synergistic effect of Mo -CBP 3 -PepI and Ciprofloxacin against Staphylococcus aureus biofilms - Nilton A. S. Neto; Tawanny K. B. Aguiar; Rayara J. P. Costa; Felipe P. Mesquita; Lais L. B. de Oliveira; Maria E. A. de Moraes; Raquel C. Montenegro; Rômulo F. Carneiro; Celso S. Nagano; Cleverson D. T. Freitas; Pedro F. N. Souza (Biofouling, 2023)

Preliminary assessment of toxicity of aerosol samples from central-west Brazil using Artemia spp. bioassays - Habdias A. Silva-Neto; Valtencir Zucolotto; Emmanuel B. D'Alessandro; Maria G.O. Tavares; Nelson R. Antoniosi Filho; Wendell K.T. Coltro; Guilherme M. Grosseli; Pedro S. Fadini; Roberta C. Urban (Chemosphere, 2023)

Ficus sect. Americanae ser. Kinuppii: a ramiflorous group of Neotropical fig trees - Leandro C. Pederneiras; Henrique B. Zamengo; Angelo Danilo Plata-Castro; Sergio Romaniuc-Neto; Vidal De F. Mansano (Brittonia, 2023)

Kinetics, mechanism, and tautomerism in ametryn acid hydrolysis: From molecular structure to environmental impacts - Bruno Ramos; Wesley F. Vaz; Luan F. Diniz; Flavio O. Sanches Neto; Julio C.O. Ribeiro; Valter H. Carvalho-Silva; Antonio Carlos S.C. Teixeira; Caue Ribeiro; Hamilton B. Napolitano; Paulo S. Carvalho (Chemosphere, 2023)

An additional threat to populations predicted to collapse: Organobromine compounds of natural and anthropogenic sources in rough-toothed dolphins from the Southwestern Atlantic Ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Camila Domit; Eduardo R. Secchi; Silvina Botta; Haydée A. Cunha; Alexandre F. Azevedo; Tatiana L. Bisi; José Lailson-Brito (Chemosphere, 2023)

Diverse urban pollinators and where to find them - Victor H.D. Silva; Ingrid N. Gomes; João C.F. Cardoso; Camila Bosenbecker; Jéssica L.S. Silva; Oswaldo Cruz-Neto; Willams Oliveira; Alyssa B. Stewart; Ariadna V. Lopes; Pietro K. Maruyama (Biological Conservation, 2023)

Retrieving records of a rare and threatened shark in a mosaic of marine‐protected areas of southeastern Brazil - Paulo R. S. Santos; Kaliandra Klafke; Otto B. F. Gadig; Domingos Garrone‐Neto (Journal of Fish Biology, 2023)
In this study the authors use the Fishers ecological knowledge (FEK) from the south coast of the São Paulo State, in southeastern Brazil, to recover records of Atlantic nurse shark ( Ginglymostoma cirratum ), a threatened with extinction species, in a mosaic of marine‐protected areas (MPAs) of the south coast of São Paulo, in southeastern Brazil, in the southernmost distribution of the species in the Southwest Atlantic Ocean. For half a century, in the study area only one male of G. cirratum was officially recorded, in 1967. Retrieving records from artisanal fishers, recreational anglers, fishing guides and spearfishers added 30 more records of G. cirratum , including 2 recent captures (February/2022 and May/2022), especially around coastal islands that are covered by MPAs. Two uncommon fishing techniques, but which provided the highest number of records for the species, were documented. These are fishing nets and small longlines adapted for fishing close to the rocks, being an apparently traditional activity of a few natives of the region. As Brazil has a long history of intense catches of threatened elasmobranchs and problems with fisheries monitoring, the consideration of the FEK in the fisheries monitoring carried out by the authorities can be useful to promote improvements in data collection, especially of rare and endangered species such as G. cirratum . The strengthening of the protection of the MPAs and the articulation of research and management institutions with native people and tourists who use these areas should also be considered.

Epidemiological and clinicopathological findings in 15 fatal outbreaks of salmonellosis in dairy calves and virulence genes in the causative Salmonella enterica Typhimurium and Dublin strains - ML. Casaux; W. Santiago Neto; CO. Schild; RA. Costa; M. Macías-Rioseco; RD. Caffarena; CS. Silveira; V. Aráoz; B. Doncel Díaz; F. Giannitti; M. Fraga (Brazilian Journal of Microbiology, 2023)

Addition of raw feedstocks and biochars to the soil on the sorption–desorption and biodegradation of 14C-saflufenacil - F. S. de Oliveira; V. Takeshita; K. F. Mendes; V. L. Tornisielo; F. G. Alonso; L. V. Junqueira; M. B. Neto; H. A. Lins; D. V. Silva (International Journal of Environmental Science and Technology, 2023)

Ovarian morphology and oocyte development in the seabob shrimp Xiphopenaeus kroyeri: a histological and histochemical approach for the study of penaeid reproduction - Cecília Craveiro; Hildemário Castro-Neto; Larissa B. Costa; Emanuell F. Silva; Paulo G.V. de Oliveira; Lucas Santos; Roberta Soares; Silvio Peixoto (Aquaculture, 2023)

High-throughput phenotyping by deep learning to include body shape in the breeding program of pacu (Piaractus mesopotamicus) - Milena V. Freitas; Celma G. Lemos; Raquel B. Ariede; John F.G. Agudelo; Rubens R.O. Neto; Carolina H.S. Borges; Vito A. Mastrochirico-Filho; Fábio Porto-Foresti; Rogério L. Iope; Fabrício M. Batista; José R.F. Brega; Diogo T. Hashimoto (Aquaculture, 2023)

Characterization of Multidrug-Resistant Staphylococcus aureus Isolates and Comparison of Methods of Susceptibility to Vancomycin - Danillo S. Rosa; Samily A. S. Oliveira; Renata F. S. Souza; Amaro A. S. Neto; Letícia S. B. Cunha; Antônio W. C. Fernandes; Ianka F. S. Soares; Sarah K. R. Teixeira; Samuel R. Aquino; Gisele V. Gouveia; Jackson R. G. S. Almeida; Carine R. Naue; et al. (Current Microbiology, 2022)

Molecular Detection of Rickettsia parkeri Strain Atlantic Rainforest in Ticks Parasitizing Small Mammals in Northeastern Brazil - Josiane M. Rocha; Philipe B. de Oliveira; Sócrates F. da Costa-Neto; Maria H. Ogrzewalska; Thiago F. Martins; João L. H. Faccini; Martin R. D. V. Alvarez; Hermes R. Luz; George R. Albuquerque (Acta Parasitologica, 2022)

Large groups of Atlantic spotted dolphin ( Stenella frontalis ) in a coastal bay from southeastern Brazil - Karina S. Pereira; Rafael R. Carvalho; Camila L. P. Rosa; Elitieri B. Santos‐Neto; José Lailson‐Brito,; Tatiana L. Bisi; Alexandre F. Azevedo (Marine Mammal Science, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Urban afforestation: using phytotoxicity endpoints to compare air pollution tolerance of two native Brazilian plants Aroeira (Schinus terebinthifolius) and Cuvatã (Cupania vernalis) - Renata F. Storch-Böhm; Cleder A. Somensi; Renan C. Testolin; Überson B. Rossa; Rogério Corrêa; Rafael Ariente-Neto; Gizelle I. Almerindo; Jean-François Férard; Sylvie Cotelle; Claudemir M. Radetski (Environmental Science and Pollution Research, 2022)

Influence of temperature on the toxicity of the elutriate from a pesticide contaminated soil to two cladoceran species - Livia Pitombeira de Figueirêdo; Danillo B. Athayde; Thandy Junio da Silva Pinto; Michiel A. Daam; Glauce da Silva Guerra; Paulo José Duarte-Neto; Evaldo L. G. Espíndola (Ecotoxicology, 2022)

Identification of potential new mosquito-associated viruses of adult Aedes aegypti mosquitoes from Tocantins state, Brazil - Matheus A. Duarte; Fabrício S. Campos; Osvaldo F. Araújo Neto; Leonardo A. Silva; Arthur B. Silva; Thalita C. Aguiar; Raissa N. Santos; Ueric J. B. Souza; Giselly B. Alves; Fernando L. Melo; Daniel M. P. Ardisson-Araujo; Raimundo W. S. Aguiar; et al. (Brazilian Journal of Microbiology, 2022)

Adaptation Strategy to Increase the Tolerance of Scheffersomyces stipitis NRRL Y-7124 to Inhibitors of Sugarcane Bagasse Hemicellulosic Hydrolysate Through Comparative Studies of Proteomics and Fermentation - Luiz E. Biazi; Samantha C. Santos; Antonio A. Kaupert Neto; Amanda S. Sousa; Lauren B. Soares; Eduardo Renzano; Juliana Velasco; Sarita C. Rabelo; Aline C. Costa; Jaciane L. Ienczak (BioEnergy Research, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Epidemiological features of the first Unusual Mortality Event linked to cetacean morbillivirus in the South Atlantic (Brazil, 2017–2018) - Haydée A. Cunha; Elitieri B. Santos‐Neto; Rafael R. Carvalho; Joana M. P. Ikeda; Katia R. Groch; Josué Díaz‐Delgado; Emi B. Guari; Juliana A. Brião; Raissa B. Oliveira; Leonardo Flach; Tatiana L. Bisi; José L. Catão‐Dias; et al. (Marine Mammal Science, 2021)
Since the 1980s, cetacean morbillivirus (CeMV) has caused mass mortality events worldwide. However, no epizootics had been recorded in the South Atlantic, until an unusual mortality event (UME) linked to Guiana dolphin cetacean morbillivirus (GD‐CeMV) began in Ilha Grande Bay, southeastern Brazil, in November 2017. In a five‐month period, the UME spread to neighboring Sepetiba Bay and accounted for the death of at least 277 Guiana dolphins ( Sotalia guianensis ). Prevalence of morbillivirus positive dolphins, as estimated from RT‐PCR diagnostics, was 92.3% (24/26) in Ilha Grande Bay and 91.9% (57/62) in Sepetiba Bay. Females had higher mortality rates during the UME (1.5:1), in contrast with historical mortality data from both bays that showed a 2:1 male to female death ratio. Calf mortality rates also increased in both bays. These results suggest that females and calves were more vulnerable to morbilliviral infection. Herein, we discuss possible explanations for such sex‐biased death pattern during the UME and their implication for the conservation of endangered Guiana dolphins. We also speculate about the origin and spread of morbillivirus in the South Atlantic Ocean.

Additional Pressure to a Threatened Species: High Persistent Organic Pollutant Concentrations in the Tropical Estuarine Batoid Gymnura altavela - L. G. Paiva; M. Vannuci-Silva; B. Correa; E. Santos-Neto; M. Vianna; J. L. Lailson-Brito (Bulletin of Environmental Contamination and Toxicology, 2021)

Assessment of climate change impacts on hydrology and water quality of large semi-arid reservoirs in Brazil - João B. S. Raulino; Cleiton S. Silveira; Iran Eduardo Lima Neto (Hydrological Sciences Journal, 2021)

Carbapenem-resistant Enterobacteriaceae among kidney transplant recipients – insights on the risk of acquisition and CRE infection - Maristela P. Freire; Laina B. Carvalho; Jose Otto Reusing; Fernanda Spadão; Max Igor B. F. Lopes; William C. Nahas; Elias David-Neto; Ligia C. Pierrotti (Infectious Diseases, 2021)

Storage of Brazilian Cattleya seeds from diverse biomes: lipid composition and effects on germination - Mariane M. Hengling; Thiago M. R. Gianeti; Silvério T. Hosomi; Nelson B. Machado-Neto; Ceci C. Custódio (Plant Biosystems, 2021)

Marine Streptomyces sp. Isolated From the Brazilian Endemic Tunicate Euherdmania sp. Produces Dihydroeponemycin and Analogs With Potent Antiglioma Activity - Luciana C. Furtado; Anelize Bauermeister; Rafael de Felicio; Raquel Ortega; Francisco das Chagas L. Pinto; João Agostinho Machado-Neto; Daniela B. B. Trivella; Otilia D. L. Pessoa; Diego V. Wilke; Norberto P. Lopes; Paula C. Jimenez; Leticia V. Costa-Lotufo (Frontiers in Marine Science, 2021)
Marine natural products have emerged as an important source for drug development, notably in the field of anticancer therapy. Still, the limited effectiveness of current therapies for central nervous system tumors indicates the need to identify new therapeutic targets and also novel pharmacological agents. In this context, proteasome inhibitors are appearing as a promising new treatment for these diseases. Herein, cytotoxic extracts produced by four marine bacteria recovered from the Brazilian endemic ascidian Euherdmania sp. were screened to evaluate their potential as proteasome inhibitors. The extract from marine Streptomyces sp. BRA-346 was selected for further investigation due to the potent proteasome inhibitory activity it displayed. Bioassay-guided fractionation led to an enriched fraction (proteasome inhibition IC 50 = 45 ng/mL), in which the presence of dihydroeponemycin (DHE), known for its proteasome inhibitory effect, and related compounds were annotated by mass spectrometry and further confirmed by comparison with DHE standard. Both DHE and the epoxyketone-containing fraction were evaluated in glioma cell lines, displaying high cytotoxicity in HOG and T98G cells (GI 50 of 1.6 and 1.7 ng/mL for DHE, and 17.6 and 28.2 ng/mL for the BRA-346 fraction, respectively). Additional studies showed that the epoxyketone-containing fraction (at GI 50 levels) led to an accumulation of ubiquitinated proteins and up-regulation of genes related to ER-stress response, suggesting treated cells are under proteasome inhibition. DHE induced similar effects in treated cells but at concentrations 25 times its GI 50 , suggesting that the other epoxyketone compounds in the bacteria extract derived fraction may contribute to enhance proteasome inhibition and further cellular effects in glioma cells. These findings revealed the molecular pathways modulated by this class of compounds in glioma cells and, moreover, reinforced the potential of this marine bacteria in producing a cocktail of structurally-related compounds that affect the viability of glioma cells.

Potentiation of Antibiotic Activity by a Meldrum’s Acid Arylamino Methylene Derivative against Multidrug-Resistant Bacterial Strains - Maria M. C. da Silva; José B. de Araújo-Neto; Ana C. J. de Araújo; Priscilla R. Freitas; Cícera D. de M. Oliveira-Tintino; Iêda M. Begnini; Ricardo A. Rebelo; Luiz E. da Silva; Sandro L. Mireski; Michele C. Nasato; Maria I. L. Krautler; Jaime Ribeiro-Filho; et al. (Indian Journal of Microbiology, 2021)

Morphological, productive, and nutritional characterization of Desmanthus spp. accessions under different cutting intensities - Williane P. S. Diniz; Mércia V. F. Santos; Antonia S. C. Verás; Márcio V. Cunha; Djalma E. Simões Neto; Toni C. Souza; José C. B. Dubeux; Daciele S. Abreu; Rinaldo L. C. Ferreira (Agroforestry Systems, 2021)

Reduced cutaneous inflammation associated with antioxidant action after topical application of the aqueous extract of Annona muricata leaves - Luana M. Cercato; Jéssica M. D. Araújo; Alan S. Oliveira; Allan J. O. Melo; Bruno S. Lima; Edmilson W. P. dos Santos; Agenor G. dos S. Neto; Ricardo L. C. de Albuquerque-Júnior; Marcelo C. Duarte; Adriano A. S. Araujo; Ana Mara O. Silva; Renata Grespan; et al. (Inflammopharmacology, 2021)

Exploratory analysis in the evaluation of stress due to aluminum presence in Physalis angulata L. and multielement determination by microwave-induced plasma optical emission spectrometry (MIP OES) - Claudia B. de Abreu; Marcos de O. Ribeiro; Cyndi S. Pinho; Candice N. Carneiro; André D. de Azevedo Neto; Manuela O. de Souza; Fabio de S. Dias (Environmental Science and Pollution Research, 2021)

Evaluation of bioavailability of trace metals through bioindicators in a urbanized estuarine system in southeast Brazil - K. S. Vieira; M. A. C. Crapez; L. S. Lima; J. F. Delgado; E. B. C. C. Brito; E. M. Fonseca; J. A. Baptista Neto; V. M. C. Aguiar (Environmental Monitoring and Assessment, 2021)

Correction to: α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

α-Phellandrene attenuates tissular damage, oxidative stress, and TNF-α levels on acute model ifosfamide-induced hemorrhagic cystitis in mice - R. L. G. Gonçalves; F. V. M. Cunha; B. P. S. Sousa-Neto; L. S. A. Oliveira; M. E. Lopes; D. C. Rezende; I. J. O. Sousa; K. M. Nogueira; L. K. M. Souza; J. V. R. Medeiros; D. V. T. Wong; V. M. P. Pereira; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Protective effect of nutraceutical food on the intestinal mucosa of juvenile pacu Piaractus mesopotamicus under high stocking density - Mariana C. F. Pontin; Wiolene M. Nordi; Jéssica Pampolini; Raul Machado-Neto; Débora B. Moretti (Aquaculture International, 2020)

Storage of orchid pollinia with varying lipid thermal fingerprints - Ceci Castilho Custodio; Nelson B. Machado-Neto; Rodrigo B. Singer; Hugh W. Pritchard; Philip T. Seaton; Timothy R. Marks (Protoplasma, 2020)

How Does the Landscape Affect Metacommunity Structure? A Quantitative Review for Lentic Environments - Mauricio Almeida-Gomes; Francisco Valente-Neto; Eduardo O. Pacheco; Carolina C. Ganci; Mathew A. Leibold; Adriano S. Melo; Diogo B. Provete (Current Landscape Ecology Reports, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Neotropical endemism and dispersal events between tropical and extra‐tropical regions underlay the reticulate assemblages of muscid flies - Peter Löwenberg‐Neto; Claudio J. B. de Carvalho (Journal of Biogeography, 2020)
Aim The housefly family Muscidae originated during the Paleocene–Eocene and is currently distributed worldwide. We investigated how muscid genera have assembled in the continents by historical dispersal events. Location Global (except Antarctica). Taxon Muscidae, Diptera, Insecta. Methods We compiled a dataset of 181 species, which provided geographic information for 67 genera as terminals. Phylogenetic and geographic data were fitted by five dispersal–extinction–cladogenesis models based on dispersal constraints. Based on the event inferences of the best‐fit model, we quantified the direction and frequency of dispersals through time in absolute numbers and in relation to the number of lineages. Results The best‐fit model was ‘unrestricted routes’, which inferred 48 events of dispersals: 66% were trans‐climatic events and 81% were transoceanic events. The direction of the dispersals was strongly asymmetric: the Neotropical (NEO) region was the primary source of lineages for all other regions and the Palearctic (PAL) was the secondary source. The relative frequency of dispersal events through time plot was marked by three phases: the early peak of the frequency (40–35 million years ago [Ma]), a valley of low frequencies (30–20 Ma), and the recent peak (15–5 Ma). Trans‐climatic dispersals from the NEO to the PAL region occurred in all phases. Lineages of the Cyrtoneurininae showed a low frequency of dispersal events and most of the terminals (11 of 15) were endemic to the NEO region. Conclusion The Muscidae family originated in the Neotropical region and more recent dispersal events to the Palearctic region established the scenario for lineages to diversify and spread worldwide. Trans‐climatic dispersals were more frequent than cis‐events and tropical niche conservatism was not the underlying mechanism for the whole clade. We showed that dispersal events between biogeographic regions of the same and different climatic zones were required to achieve the current distribution of extant genera of muscids across the globe.

Sugarcane straw management for bioenergy: effects of global warming on greenhouse gas emissions and soil carbon storage - Gustavo V. Popin; Arthur K. B. Santos; Thiago de P. Oliveira; Plínio B. de Camargo; Carlos E. P. Cerri; Marcos Siqueira-Neto (Mitigation and Adaptation Strategies for Global Change, 2020)

Effect of Additives to Improve Calcium-Based Sorbents in Semi-Dry Flue Gas Desulphurization - Ítalo W. L. França; Samuel J. M. Cartaxo; Moises Bastos-Neto; Luciana R. B. Gonçalves; Fabiano A. N. Fernandes (Emission Control Science and Technology, 2020)

Cultivable fungi present in deep-sea sediments of Antarctica: taxonomy, diversity, and bioprospecting of bioactive compounds - Mayara B. Ogaki; Lívia C. Coelho; Rosemary Vieira; Arthur A. Neto; Carlos L. Zani; Tânia M. A. Alves; Policarpo A. S. Junior; Silvane M. F. Murta; Emerson C. Barbosa; Jaquelline G. Oliveira; Isabela P. Ceravolo; Patrícia O. Pereira; et al. (Extremophiles, 2020)

Natural Vs Managed Habitat: Effect Over the Seed-Predator Pachymerus nucleorum and Its Natural Enemies - J O S Silva; M L E Costa; B S Paixão; J D B Macêdo; P M S Rodrigues; E M F Lins-Neto (Neotropical Entomology, 2020)

Long-term chromium picolinate supplementation improves colostrum profile of Santa Ines ewe - Thiago F. V. Bompadre; Débora B. Moretti; Gabriel Z. Sakita; Egon H. Ieda; Maria I. V. Martinez; Elisabete A. N. Fernandes; Raul Machado-Neto; Adibe L. Abdalla; Helder Louvandini (Biological Trace Element Research, 2020)

Guanosine and GMP increase the number of granular cerebellar neurons in culture: dependence on adenosine A2A and ionotropic glutamate receptors - Helena Decker; Tetsade C. B. Piermartiri; Cláudia B. Nedel; Luciana F. Romão; Sheila S. Francisco; Tharine Dal-Cim; Carina R. Boeck; Vivaldo Moura-Neto; Carla I. Tasca (Purinergic Signalling, 2019)

Which Species of Coconut Moth Occurs in Brazil: Atheloca subrufella vs. Atheloca bondari (Lepidoptera: Pyralidae)? - A A Paz-Neto; M. T. S. Freitas; M. G. C. Gondim; J. W. S. Melo; R. B. Querino; V. Q. Balbino (Neotropical Entomology, 2019)

The citrus flavanone naringenin attenuates zymosan-induced mouse joint inflammation: induction of Nrf2 expression in recruited CD45+ hematopoietic cells - Allan J. C. Bussmann; Sergio M. Borghi; Tiago H. Zaninelli; Telma S. dos Santos; Carla F. S. Guazelli; Victor Fattori; Talita P. Domiciano; Felipe A. Pinho-Ribeiro; Kenji W. Ruiz-Miyazawa; Antonio M. B. Casella; Josiane A. Vignoli; Doumit Camilios-Neto; et al. (Inflammopharmacology, 2019)

Crop, livestock and forestry performance assessment under different production systems in the north of Mato Grosso, Brazil - C. A. S. Magalhães; B. C. Pedreira; H. Tonini; A. L. Farias Neto (Agroforestry Systems, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

A Review of High Impact Weather for Aviation Meteorology - Ismail Gultepe; R. Sharman; Paul D. Williams; Binbin Zhou; G. Ellrod; P. Minnis; S. Trier; S. Griffin; Seong. S. Yum; B. Gharabaghi; W. Feltz; M. Temimi; et al. (Pure and Applied Geophysics, 2019)

Gene expression and spatiotemporal localization of antifungal chitin-binding proteins during Moringa oleifera seed development and germination - Tarcymara B. Garcia; Arlete A. Soares; Jose H. Costa; Helen P. S. Costa; João X. S. Neto; Lady Clarissa B. Rocha-Bezerra; Fredy Davi A. Silva; Mariana R. Arantes; Daniele O. B. Sousa; Ilka M. Vasconcelos; Jose T. A. Oliveira (Planta, 2019)

Divergent coronaviruses detected in wild birds in Brazil, including a central park in São Paulo - Carla M. Barbosa; Edison L. Durigon; Luciano M. Thomazelli; Tatiana Ometto; Roberta Marcatti; Marcello Shiavo Nardi; Daniel M. de Aguiar; João Batista Pinho; Maria Virginia Petry; Isaac Simão Neto; Patrícia Serafini; Roberta Costa Rodrigues; et al. (Brazilian Journal of Microbiology, 2019)

Studies of NMR, molecular docking, and molecular dynamics simulation of new promising inhibitors of cruzaine from the parasite Trypanosoma cruzi - Renato A. Costa; Jorddy N. Cruz; Fabiana C. A. Nascimento; Sebastião G. Silva; Silvana O. Silva; Marlice C. Martelli; Samira M. L. Carvalho; Cleydson B. R. Santos; Antonio M. J. C. Neto; Davi S. B. Brasil (Medicinal Chemistry Research, 2019)

Use of mucus as a non‐invasive sampling method for DNA barcoding of stingrays and skates (batoid elasmobranchs) - Rodrigo R. Domingues; Domingos Garrone‐Neto; Alexandre W. S. Hilsdorf; Otto B. F. Gadig (Journal of Fish Biology, 2019)
In this study we tested the use of mucus from five species of Neotropical marine batoid elasmobranchs to extract genomic DNA for barcoding and phylogenetic analysis. The DNA from all individuals sampled was successfully amplified and sequenced for molecular barcode, allowing 99–100% accuracy to the species level. This method proved to provide reliable and good‐quality DNA for barcoding and phylogenetic analysis of Neotropical elasmobranchs, through rapid handling and with low disturbance to animals.

A trypsin inhibitor from Moringa oleifera flower extract is cytotoxic to Trypanosoma cruzi with high selectivity over mammalian cells - Emmanuel V. Pontual; Divar F. Pires-Neto; Karina Fraige; Taciana M. M. Higino; Belany E. A. Carvalho; Neyla M. P. Alves; Thâmarah A. Lima; Russolina B. Zingali; Luana C. B. B. Coelho; Vanderlan S. Bolzani; Regina C. B. Q. Figueiredo; Thiago H. Napoleão; et al. (Natural Product Research, 2018)

Immediate effects of transcutaneous electrical nerve stimulation (TENS) administered during resistance exercise on pain intensity and physical performance of healthy subjects: a randomized clinical trial - Mayara A. Menezes; Thaís A. B. Pereira; Leonardo M. Tavares; Belissa T. Q. Leite; Antônio G. R. Neto; Leury M. S. Chaves; Lucas V. Lima; Marzo E. Da Silva-Grigolleto; Josimari M. DeSantana (European Journal of Applied Physiology, 2018)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

Laser-based spectroscopic methods to evaluate the humification degree of soil organic matter in whole soils: a review - Giorgio S. Senesi; Ladislau Martin-Neto; Paulino Ribeiro Villas-Boas; Gustavo Nicolodelli; Débora M. B. P. Milori (Journal of Soils and Sediments, 2018)

How complex should models be? Comparing correlative and mechanistic range dynamics models - Damien A. Fordham; Cleo Bertelsmeier; Barry W. Brook; Regan Early; Dora Neto; Stuart C. Brown; Sébastien Ollier; Miguel B. Araújo (Global Change Biology, 2018)
Criticism has been levelled at climate‐change‐induced forecasts of species range shifts that do not account explicitly for complex population dynamics. The relative importance of such dynamics under climate change is, however, undetermined because direct tests comparing the performance of demographic models vs. simpler ecological niche models are still lacking owing to difficulties in evaluating forecasts using real‐world data. We provide the first comparison of the skill of coupled ecological‐niche‐population models and ecological niche models in predicting documented shifts in the ranges of 20 British breeding bird species across a 40‐year period. Forecasts from models calibrated with data centred on 1970 were evaluated using data centred on 2010. We found that more complex coupled ecological‐niche‐population models (that account for dispersal and metapopulation dynamics) tend to have higher predictive accuracy in forecasting species range shifts than structurally simpler models that only account for variation in climate. However, these better forecasts are achieved only if ecological responses to climate change are simulated without static snapshots of historic land use, taken at a single point in time. In contrast, including both static land use and dynamic climate variables in simpler ecological niche models improve forecasts of observed range shifts. Despite being less skilful at predicting range changes at the grid‐cell level, ecological niche models do as well, or better, than more complex models at predicting the magnitude of relative change in range size. Therefore, ecological niche models can provide a reasonable first approximation of the magnitude of species' potential range shifts, especially when more detailed data are lacking on dispersal dynamics, demographic processes underpinning population performance, and change in land cover.

Modulation of antibiotic activity by the hydroalcoholic extract from leaves of Caryocar coriaceum WITTM - Luís J. de Lacerda Neto; A. G. B. Ramos; M. R. Kerntopf; H. D. M. Coutinho; L. J. Quintans-Junior; J. R. G. S. Almeida; J. Ribeiro-Filho; I. R. A. Menezes (Natural Product Research, 2018)

Ticks (Acari: Ixodidae) of the state of Amazonas, Brazil - Sergio L. Gianizella; Thiago F. Martins; Valeria C. Onofrio; Nair O. Aguiar; Waleska Gravena; Carlos A. R. do Nascimento; Laérzio C. Neto; Diogo L. Faria; Natália A. S. Lima; Monica R. Solorio; Louise Maranhão; Ivan J. Lima; et al. (Experimental and Applied Acarology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

The impacts of a plume-rise scheme on earth system modeling: climatological effects of biomass aerosols on the surface temperature and energy budget of South America - Otacilio L. de Menezes Neto; Mariane M. Coutinho; José A. Marengo; Vinícius B. Capistrano (Theoretical and Applied Climatology, 2017)

Design of Magnetic Polymeric Particles as a Stimulus-Responsive System for Gastric Antimicrobial Therapy - Erica L. Silva-Freitas; Thales R. F. Pontes; Rafael P. Araújo-Neto; Ítalo H. M. Damasceno; Kátia L. Silva; Juliana F. Carvalho; Aldo C. Medeiros; Rodolfo B. Silva; Amanda K. A. Silva; Marco A. Morales; Eryvaldo S. T. Egito; Ana L. Dantas; et al. (AAPS PharmSciTech, 2017)

Structural and ultrastructural characterization of the spermatozoa in Pachycondyla striata and P. marginata - L. Cuquetto-Leite; H. Dolder; P. S. Oliveira; N. B. Espírito Santo; J. Lino-Neto; K. C. Mancini (Insectes Sociaux, 2017)

Labeling of adipose-derived stem cells with quantum dots provides stable and long-term fluorescent signal for ex vivo cell tracking - Clautina R. M. Costa; Matheus L. T. Feitosa; Dayseanny O. Bezerra; Yulla K. P. Carvalho; Rodrigo F. G. Olivindo; Pablo B. Fernando; Gustavo C. Silva; Mirna L. G. Silva; Carlos E. Ambrósio; Airton M. Conde Júnior; Napoleão M. Argolo Neto; Laís M. Costa Silva; et al. (In Vitro Cellular & Developmental Biology - Animal, 2017)

Effects of competition on fitness-related traits - A. D. Smith; A. L. S. Houde; B. Neff; P. R. Peres-Neto (Oecologia, 2017)

Degradation of Direct Red 81 mediated by Fenton reactions: multivariate optimization, effect of chloride and sulfate, and acute ecotoxicity assessment - Eduardo O. Marson; Vinícius A. B. de Paiva; Bárbara R. Gonçalves; Oswaldo Gomes Júnior; Waldomiro Borges Neto; Antonio E. H. Machado; Alam G. Trovó (Environmental Science and Pollution Research, 2017)

Microbial diversity in degraded and non-degraded petroleum samples and comparison across oil reservoirs at local and global scales - Isabel Natalia Sierra-Garcia; Bruna M. Dellagnezze; Viviane P. Santos; Michel R. Chaves B; Ramsés Capilla; Eugenio V. Santos Neto; Neil Gray; Valeria M. Oliveira (Extremophiles, 2017)

Treatment of an industrial stream containing vinylcyclohexene by the H2O2/UV process - Lenise V. F. Gonçalves; Eduardo B. Azevedo; Francisco R. de Aquino-Neto; Daniele M. Bila; Geraldo L. Sant’Anna; Márcia Dezotti (Environmental Science and Pollution Research, 2016)

Influence of the current density on the electrochemical treatment of concentrated 1-butyl-3-methylimidazolium chloride solutions on diamond electrodes - Suzana M. L. de Oliveira Marcionilio; Gisele M. Alves; Rachel B. Góes e Silva; Pablo J. Lima Marques; Poliana D. Maia; Brenno A. D. Neto; José J. Linares (Environmental Science and Pollution Research, 2016)

RNA‐seq analyses reveal insights into the function of respiratory nitrate reductase of the diazotroph Herbaspirillum seropedicae - Paloma Bonato; Marcelo B. Batista; Doumit Camilios‐Neto; Vânia C. S. Pankievicz; Michelle Z. Tadra‐Sfeir; Rose Adele Monteiro; Fabio O. Pedrosa; Emanuel M. Souza; Leda S. Chubatsu; Roseli Wassem; Liu Un Rigo (Environmental Microbiology, 2016)
Summary Herbaspirillum seropedicae is a nitrogen‐fixing β‐proteobacterium that associates with roots of gramineous plants. In silico analyses revealed that H. seropedicae genome has genes encoding a putative respiratory (NAR) and an assimilatory nitrate reductase (NAS). To date, little is known about nitrate metabolism in H. seropedicae , and, as this bacterium cannot respire nitrate, the function of NAR remains unknown. This study aimed to investigate the function of NAR in H. seropedicae and how it metabolizes nitrate in a low aerated‐condition. RNA‐seq transcriptional profiling in the presence of nitrate allowed us to pinpoint genes important for nitrate metabolism in H. seropedicae , including nitrate transporters and regulatory proteins. Additionally, both RNA‐seq data and physiological characterization of a mutant in the catalytic subunit of NAR ( narG mutant) showed that NAR is not required for nitrate assimilation but is required for: (i) production of high levels of nitrite, (ii) production of NO and (iii) dissipation of redox power, which in turn lead to an increase in carbon consumption. In addition, wheat plants showed an increase in shoot dry weight only when inoculated with H. seropedicae wild type, but not with the narG mutant, suggesting that NAR is important to H. seropedicae ‐wheat interaction.

Apple scab control and activation of plant defence responses using potassium phosphite and chitosan - Ricardo B. Felipini; José I. Boneti; Yoshinori Katsurayama; Argus C. Rocha Neto; Beatriz Veleirinho; Marcelo Maraschin; Robson M. Di Piero (European Journal of Plant Pathology, 2016)

Antimicrobial Activity of ILTI, a Kunitz‐Type Trypsin Inhibitor from Inga laurina (SW.) Willd - Maria Lígia R. Macedo; Suzanna F. F. Ribeiro; Gabriel B. Taveira; Valdirene M. Gomes; Karina M. C. A. de Barros; Simone Maria-Neto (Current Microbiology, 2016)

Rhizopus arrhizus and Fusarium solani Concomitant Infection in an Immunocompromised Host - João N. de Almeida Júnior; Karim Y. Ibrahim; Gilda M. B. Del Negro; Evandro D. Bezerra; Amaro N. Duarte Neto; Marjorie V. Batista; Rinaldo F. Siciliano; Mauro C. Giudice; Adriana L. Motta; Flávia Rossi; Ligia C. Pierrotti; Maristela P. Freire; et al. (Mycopathologia, 2016)

Effect of diets enriched with rutin on blood parameters, oxidative biomarkers and pituitary hormone expression in silver catfish (Rhamdia quelen) - Tanise S. Pês; Etiane M. H. Saccol; Giovana M. Ourique; Érika P. Londero; Luciane T. Gressler; Isabela A. Finamor; Daniel A. Rotili; Jaqueline I. Golombieski; Werner G. Glanzner; Susana F. Llesuy; Paulo B. D. Gonçalves; João Radünz Neto; et al. (Fish Physiology and Biochemistry, 2016)

The phylogeny and evolutionary history of the Lesion Simulating Disease (LSD) gene family in Viridiplantae - Caroline Cabreira; Alexandro Cagliari; Lauro Bücker-Neto; Márcia Margis-Pinheiro; Loreta B. de Freitas; Maria Helena Bodanese-Zanettini (Molecular Genetics and Genomics, 2015)

Neonatal Candidemia Caused by Candida haemulonii: Case Report and Review of Literature - Carolina M. Silva; Ana M. R. Carvalho-Parahym; Danielle P. C. Macêdo; Reginaldo G. Lima-Neto; Elaine C. Francisco; Analy S. A. Melo; Maria da Conceição M. Silva; Moacir B. Jucá; Luciana R. B. Mello; Rosemary M. J. Amorim; Rejane P. Neves (Mycopathologia, 2015)

First microsatellite markers for Lecythis pisonis (Lecythidaceae), an important resource for Brazilian fauna - Acácia B. Rodrigues; Ciro Tavares Florence; Eduardo Mariano-Neto; Fernanda A. Gaiotto (Conservation Genetics Resources, 2015)

Assessing families’ and patients’ attitudes toward brain donation for research purposes in a Brazilian population sample - M. K. Fonseca; E. Rodrigues-Neto; A. S. R. Costa; M. A. B. C. Rockembach; R. S. Padilha; L. L. Fernandez; F. H. Oliveira; L. P. Garcia; A. Hilbig (Cell and Tissue Banking, 2015)

Surveillance of Azole Resistance Among Candida spp. as a Strategy for the Indirect Monitoring of Freshwater Environments - Raimunda S. N. Brilhante; Manoel A. N. Paiva; Célia M. S. Sampaio; Débora S. C. M. Castelo-Branco; Lucas P. Alencar; Tereza J. P. G. Bandeira; Rossana A. Cordeiro; Waldemiro de Aquino Pereira Neto; José L. B. Moreira; José J. C. Sidrim; Marcos F. G. Rocha (Water, Air, & Soil Pollution, 2015)

Development of microsatellite primers for Melanoxylon brauna (Fabaceae): an endangered and endemic tree from the Brazilian Atlantic Forest - Daniela B. Borges; Eduardo Mariano-Neto; Fernanda A. Gaiotto (Conservation Genetics Resources, 2015)

Hylax bahiensis Bechyné (Chrysomelidae: Eumolpinae): a New Potential Pest of Eucalyptus and Species Used for Atlantic Rainforest Restoration - R G Mafia; J B da Silva; J F Ramos; G V Mafia; G H Rosado-Neto; E M O Ferronatto (Neotropical Entomology, 2015)

Histochemical distribution of intestinal enzymes of juvenile pacu (Piaractus mesopotamicus) fed lyophilized bovine colostrum - Débora B. Moretti; Wiolene M. Nordi; Thaline M. P. Cruz; José Eurico P. Cyrino; Raul Machado-Neto (Fish Physiology and Biochemistry, 2014)

Neurophysiological Studies and Non-Motor Symptoms Prior to Ataxia in a Patient with Machado–Joseph Disease: Trying to Understand the Natural History of Brain Degeneration - José Luiz Pedroso; Edson Bor-Seng-Shu; Pedro Braga-Neto; Rodrigo Souza Ribeiro; Márcio Luiz Escorcio Bezerra; Lucila B. F. do Prado; Ilza Rosa Batista; Helena Alessi; Manoel Jacobsen Teixeira; Gilberto Mastrocola Manzano; Gilmar Fernandes do Prado; Orlando Graziani Povoas Barsottini (The Cerebellum, 2014)

Brazilian brown propolis elicits antileishmanial effect against promastigote and amastigote forms of Leishmania amazonensis - Lorena C.L.R. Santana; Sabrina Maria P. Carneiro; Laurentino B. Caland-Neto; Daniel D.R. Arcanjo; José M. Moita-Neto; Antônia M.G.L. Citó; Fernando Aécio A. Carvalho (Natural Product Research, 2014)

Phenylethynyl-Butyltellurium Inhibits the Sulfhydryl Enzyme Na+, K+-ATPase: An Effect Dependent on the Tellurium Atom - Caroline B. Quines; Suzan G. Rosa; José S. S. Neto; Gilson Zeni; Cristina W. Nogueira (Biological Trace Element Research, 2013)

Microsatellite markers for the endangered orchids Cattleya labiata Lindl. and C. warneri T. Moore (Orchidaceae) - Paulo Ricardo M. Almeida; M. Cristina López-Roberts; Bianca B. Zanotto Vigna; Anete P. Souza; Aristóteles Góes-Neto; Cássio van den Berg (Conservation Genetics Resources, 2013)

The Lesion Simulating Disease (LSD) gene family as a variable in soybean response to Phakopsora pachyrhizi infection and dehydration - Caroline Cabreira; Alexandro Cagliari; Lauro Bücker-Neto; Beatriz Wiebke-Strohm; Loreta B. de Freitas; Francismar C. Marcelino-Guimarães; Alexandre L. Nepomuceno; Márcia M. A. N. Margis-Pinheiro; Maria H. Bodanese-Zanettini (Functional & Integrative Genomics, 2013)

Erratum to: NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina R. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina C. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

Effects of long-term in vitro culturing of transgenic bovine donor fibroblasts on cell viability and in vitro developmental potential after nuclear transfer - F. F. Bressan; M. S. Miranda; M. C. Bajgelman; F. Perecin; L. G. Mesquita; P. Fantinato-Neto; G. F. K. Merighe; B. E. Strauss; F. V. Meirelles (In Vitro Cellular & Developmental Biology - Animal, 2013)

Selective survival of calretinin- and vasoactive-intestinal-peptide-containing nerve elements in human chagasic submucosa and mucosa - Samir Jabari; Alexandre B. M. da Silveira; Enio C. de Oliveira; Salustiano G. Neto; Karl Quint; Winfried Neuhuber; Axel Brehmer (Cell and Tissue Research, 2012)

Rethinking the relationship between nestedness and beta diversity: a comment on Baselga (2010) - Mário Almeida‐Neto; Daniella M. B. Frensel; Werner Ulrich (Global Ecology and Biogeography, 2012)
Baselga [Partitioning the turnover and nestedness components of beta diversity. Global Ecology and Biogeography , 19 , 134–143, 2010] proposed pairwise (β nes ) and multiple‐site (β NES ) beta‐diversity measures to account for the nestedness component of beta diversity. We used empirical, randomly created and idealized matrices to show that both measures are only partially related to nestedness and do not fit certain fundamental requirements for consideration as true nestedness‐resultant dissimilarity measures. Both β nes and β NES are influenced by matrix size and fill, and increase or decrease even when nestedness remains constant. Additionally, we demonstrate that β NES can yield high values even for matrices with no nestedness. We conclude that β nes and β NES are not true measures of the nestedness‐resultant dissimilarity between sites. Actually, they quantify how differences in species richness that are not due to species replacement contribute to patterns of beta diversity. Finally, because nestedness is a special case of dissimilarity in species composition due to ordered species loss (or gain), the extent to which differences in species composition is due to nestedness can be measured through an index of nestedness.

Ubiquitous urease affects soybean susceptibility to fungi - Beatriz Wiebke-Strohm; Giancarlo Pasquali; Márcia Margis-Pinheiro; Marta Bencke; Lauro Bücker-Neto; Arlete B. Becker-Ritt; Anne H. S. Martinelli; Ciliana Rechenmacher; Joseph C. Polacco; Renata Stolf; Francismar C. Marcelino; Ricardo V. Abdelnoor; et al. (Plant Molecular Biology, 2012)

Impact of coal tar pavement on polycyclic hydrocarbon distribution in lacustrine sediments from non-traditional sources - S. Froehner; D. B. de Souza; K. S. Machado; F. Falcão; C. S. Fernandes; T. Bleninger; D. M. Neto (International Journal of Environmental Science and Technology, 2012)

Water Deficit and Salt Stress Diagnosis Through LED Induced Chlorophyll Fluorescence Analysis in Jatropha curcas L. - E. A. Silva; A. S. Gouveia-Neto; R. A. Oliveira; D. S. Moura; P. C. Cunha; E. B. Costa; T. J. R. Câmara; L. G. Willadino (Journal of Fluorescence, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

The potential for hydrocarbon biodegradation and production of extracellular polymeric substances by aerobic bacteria isolated from a Brazilian petroleum reservoir - S. P. Vasconcellos; B. M. Dellagnezze; A. Wieland; J.-H. Klock; E. V. Santos Neto; A. J. Marsaioli; V. M. Oliveira; W. Michaelis (World Journal of Microbiology and Biotechnology, 2011)

Solid Dispersions of Imidazolidinedione by PEG and PVP Polymers with Potential Antischistosomal Activities - Francimary L. Guedes; Boaz G. de Oliveira; Marcelo Z. Hernandes; Carlos A. De Simone; Francisco J. B. Veiga; Maria do Carmo A. de Lima; Ivan R. Pitta; Suely L. Galdino; Pedro José Rolim Neto (AAPS PharmSciTech, 2011)

Effectiveness of Scat‐Detection Dogs in Determining Species Presence in a Tropical Savanna Landscape - CARLY VYNNE; JOHN R. SKALSKI; RICARDO B. MACHADO; MARTHA J. GROOM; ANAH T. A. JÁCOMO; JADER MARINHO‐FILHO; MARIO B. RAMOS NETO; CRISTINA POMILLA; LEANDRO SILVEIRA; HEATH SMITH; SAMUEL K. WASSER (Conservation Biology, 2011)
Most protected areas are too small to sustain populations of wide‐ranging mammals; thus, identification and conservation of high‐quality habitat for those animals outside parks is often a high priority, particularly for regions where extensive land conversion is occurring. This is the case in the vicinity of Emas National Park, a small protected area in the Brazilian Cerrado. Over the last 40 years the native vegetation surrounding the park has been converted to agriculture, but the region still supports virtually all of the animals native to the area. We determined the effectiveness of scat‐detection dogs in detecting presence of five species of mammals threatened with extinction by habitat loss: maned wolf ( Chrysocyon brachyurus ), puma ( Puma concolor ), jaguar ( Panthera onca ), giant anteater ( Myrmecophaga tridactyla ), and giant armadillo ( Priodontes maximus ). The probability of scat detection varied among the five species and among survey quadrats of different size, but was consistent across team, season, and year. The probability of occurrence, determined from the presence of scat, in a randomly selected site within the study area ranged from 0.14 for jaguars, which occur primarily in the forested areas of the park, to 0.91 for maned wolves, the most widely distributed species in our study area. Most occurrences of giant armadillos in the park were in open grasslands, but in the agricultural matrix they tended to occur in riparian woodlands. At least one target species occurred in every survey quadrat, and giant armadillos, jaguars, and maned wolves were more likely to be present in quadrats located inside than outside the park. The effort required for detection of scats was highest for the two felids. We were able to detect the presence for each of five wide‐ranging species inside and outside the park and to assign occurrence probabilities to specific survey sites. Thus, scat dogs provide an effective survey tool for rare species even when accurate detection likelihoods are required. We believe the way we used scat‐detection dogs to determine the presence of species can be applied to the detection of other mammalian species in other ecosystems.

Partial, selective survival of nitrergic neurons in chagasic megacolon - Samir Jabari; Alexandre B. M. Silveira; Enio C. Oliveira; Salustiano G. Neto; Karl Quint; Winfried Neuhuber; Axel Brehmer (Histochemistry and Cell Biology, 2011)

Prevalence of Leptospira interrogans antibodies in free-ranging Tayassu pecari of the Southern Pantanal, Brazil, an ecosystem where wildlife and cattle interact - Tatiana P. Tavares de Freitas; Alexine Keuroghlian; Donald P. Eaton; Emanuel Barbosa de Freitas; Aline Figueiredo; Luciano Nakazato; Jacqueline M. de Oliveira; Flávia Miranda; Rita Cassia S. Paes; Leticia A. R. Carneiro Monteiro; José Vergílio B. Lima; Aparecida A. da C. Neto; et al. (Tropical Animal Health and Production, 2010)

Viability and cell cycle analysis of equine fibroblasts cultured in vitro - J. F. Lima-Neto; C. B. Fernandes; M. A. Alvarenga; M. A. Golim; F. C. Landim-Alvarenga (Cell and Tissue Banking, 2010)

Burkholderia species are ancient symbionts of legumes - CYRIL BONTEMPS; GEOFFREY N. ELLIOTT; MARCELO F. SIMON; FÁBIO B. DOS REIS JÚNIOR; EDUARDO GROSS; REBECCA C. LAWTON; NICOLAU ELIAS NETO; MARIA de FÁTIMA LOUREIRO; SERGIO M. DE FARIA; JANET I. SPRENT; EUAN K. JAMES; J. PETER W. YOUNG (Molecular Ecology, 2010)

Involvement of ethylene in the rooting of seedling shoot cultures of Bixa orellana L. - Vespasiano Borges Paiva Neto; Luciano B. Reis; Fernando L. Finger; Raimundo S. Barros; Carlos R. Carvalho; Wagner C. Otoni (In Vitro Cellular & Developmental Biology - Plant, 2009)

Management of melon bacterial blotch by plant beneficial bacteria - Flávio H. V. Medeiros; Iale S. F. Moraes; Edson B. da Silva Neto; Elineide B. Silveira; Rosa de Lima R. Mariano (Phytoparasitica, 2009)

Decolorization of synthetic dyes by basidiomycetes isolated from woods of the Atlantic Forest (PE), Brazil - E. S. Lyra; K. A. Moreira; T. S. Porto; M. N. Carneiro da Cunha; F. B. Paz Júnior; B. B. Neto; J. L. Lima-Filho; M. A. Q. Cavalcanti; A. Converti; A. L. P. Porto (World Journal of Microbiology and Biotechnology, 2009)

Obesity and genetics regulate microRNAs in islets, liver, and adipose of diabetic mice - Enpeng Zhao; Mark P. Keller; Mary E. Rabaglia; Angie T. Oler; Donnie S. Stapleton; Kathryn L. Schueler; Elias Chaibub Neto; Jee Young Moon; Ping Wang; I-Ming Wang; Pek Yee Lum; Irena Ivanovska; et al. (Mammalian Genome, 2009)

The native Palythoa caribaeorum overgrows on invasive species in the intertidal zone - J. P. Mendonça-Neto; B. A. P. da Gama (Coral Reefs, 2009)

Effects of Lanthanum on Human Lymphocytes Viability and DNA Strand Break - Amanda V. Paiva; Monica S. de Oliveira; Samira N. Yunes; Leonardo G. de Oliveira; Januário B. Cabral-Neto; Carlos Eduardo B. de Almeida (Bulletin of Environmental Contamination and Toxicology, 2009)

Use of neural networks in the mathematical modelling of the enzymic synthesis of amoxicillin catalysed by penicillin G acylase immobilized in chitosan - James A. Silva; Edilson Holanda Costa Neto; Wellington S. Adriano; Andrea L. O. Ferreira; Luciana R. B. Gonçalves (World Journal of Microbiology and Biotechnology, 2008)

Linkage to chromosome 2q36.1 in autosomal dominant Dandy-Walker malformation with occipital cephalocele and evidence for genetic heterogeneity - Ali Jalali; Kimberly A. Aldinger; Ajit Chary; David G. Mclone; Robin M. Bowman; Luan Cong Le; Phillip Jardine; Ruth Newbury-Ecob; Andrew Mallick; Nadereh Jafari; Eric J. Russell; John Curran; et al. (Human Genetics, 2008)

Human Variability of fMRI Brain Activation in Response to Oculomotor Stimuli - Hellen M. Della-Justina; Bruno F. Pastorello; Taiza E. G. Santos-Pontelli; Octavio M. Pontes-Neto; Antonio Carlos Santos; Oswaldo Baffa; Jose F. Colafemina; Joao P. Leite; Draulio B. de Araujo (Brain Topography, 2008)

Structure and elastic properties of tunneling nanotubes - Bruno Pontes; Nathan B. Viana; Loraine Campanati; Marcos Farina; Vivaldo Moura Neto; H. Moysés Nussenzveig (European Biophysics Journal, 2008)

Proteome analysis of embryogenic cell suspensions of cowpea (Vigna unguiculata) - F. C. S. Nogueira; E. F. Gonçalves; E. S. Jereissati; M. Santos; J. H. Costa; O. B. Oliveira-Neto; A. A. Soares; G. B. Domont; F. A. P. Campos (Plant Cell Reports, 2007)

Genetic structure of populations of the mangrove crab Ucides cordatus (Decapoda: Ocypodidae) at local and regional scales - José F. Oliveira-Neto; Walter A. Boeger; Marcio R. Pie; Antonio Ostrensky; Diogo B. Hungria (Hydrobiologia, 2007)

Exposure of C6 glioma cells to Pb(II) increases the phosphorylation of p38MAPK and JNK1/2 but not of ERK1/2 - Thaís Posser; Cláudia B. N. Mendes de Aguiar; Ricardo C. Garcez; Francesco M. Rossi; Camila S. Oliveira; Andréa G. Trentin; Vivaldo Moura Neto; Rodrigo B. Leal (Archives of Toxicology, 2007)

Acute cattle intoxication from Nerium oleander pods - B. Soto-Blanco; J. D. Fontenele-Neto; D. M. Silva; P. F. C. C. Reis; J. E. Nóbrega (Tropical Animal Health and Production, 2006)

Valepotriates accumulation in callus, suspended cells and untransformed root cultures of Valeriana glechomifolia - Natasha Maurmann; Carina M. B. Carvalho; Andréia Loviane Silva; Arthur G. Fett-Neto; Gilsane L. Poser; Sandra B. Rech (In Vitro Cellular & Developmental Biology - Plant, 2006)

Milk-clotting protease production by Nocardiopsis sp. in an inexpensive medium - M. T. H. Cavalcanti; C. R. Martinez; V. C. Furtado; B. B. Neto; M. F. Teixeira; J. L. Lima Filho; A. L. F. Porto (World Journal of Microbiology and Biotechnology, 2005)

Control of development and valepotriate production by auxins in micropropagated Valeriana glechomifolia - C. M. Bello de Carvalho; N. Maurmann; D. I. Luz; A. G. Fett-Neto; S. B. Rech (Plant Cell Reports, 2004)

Somatic embryogenesis from immature zygotic embryos of annatto (Bixa orellana L.) - Vespasiano B. Paiva Neto; Marcel N. Botelho; Rosane Aguiar; Eldo A. M. Silva; Wagner C. Otoni (In Vitro Cellular & Developmental Biology - Plant, 2003)

Axillary bud development of passionfruit as affected by ethylene precursor and inhibitors - L. B. Reis; V. B. Paiva Neto; E. A. Toledo Picoli; M. G. C. Costa; M. M. Rêgo; C. R. Carvalho; F. L. Finger; W. C. Otoni (In Vitro Cellular & Developmental Biology - Plant, 2003)

Observing bacterial activity interferometrically - D. Faragó Jardim; R. Batista Santiago Neto; R. R. P. Machado; F. M. Aarestrup; J. P. R. F. de Mendonça; B. Lesche (European Biophysics Journal, 2003)

Zinc kinetics in insulin-dependent diabetes mellitus patients - José Brandão-Neto; Carlos A. B Silva; Nancy B. Figueiredo; T. Shuhama; Michele B.S. Holanda; Juliana M.M. Diniz (BioMetals, 2000)

Effect of zinc administration on thyrotropin releasing hormone-stimulated prolactinemia in healthy men - Ana Valéria B. Castro; Berenice B. Mendonça; Walter Bloise; Tadao Shuhama; José Brandão-Neto (BioMetals, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Carbonatites from Eastern Paraguay and genetic relationships with potassic magmatism: C, O, Sr and Nd Isotopes - F. Castorinal; P. Censi; P. Comin-Chiaramonti; E. M. Piccirillo; A. Alcover Neto; C. B. Gomes; T. I. Ribeiro de Almeida; S. Speziale; M. C. M. Toledo (Mineralogy and Petrology, 1997)

Zinc acutely and temporarily inhibits adrenal cortisol secretion in humans - J. Brandão-Neto; B. B. de Mendonça; T. Shuhama; J. S. Marchini; W. P. Pimenta; M. T. T. Tornero (Biological Trace Element Research, 1990)